Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Changing Epidemiology of Liver Involvement in Children With Celiac Disease. - Benelli, Elisa; Naviglio, Samuele; De Leo, Luigina; Stera, Giacomo; Giangreco, Manuela; Ronfani, Luca; Villanacci, Vincenzo; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Available data indicate that liver involvement is present in a significant proportion of children with celiac disease (CD) at the diagnosis (elevated transaminases 15%-57%, autoimmune liver disease 1%-2%). We sought to evaluate prevalence, clinical course, and risk factors for liver involvement in a large cohort of children with CD. METHODS: Children (age 0-18 years) diagnosed with CD from March 2010 to April 2016 were enrolled. Liver involvement was considered to be present when alanine transaminase (ALT) levels were >40 U/L (hypertransaminasemia [HTS]). Patients with HTS were re-evaluated after at least 12 months of a gluten-free diet. RESULTS: CD was diagnosed in 806 patients during the study period; of these, ALT levels were available for 700 patients (86.9%), and were elevated in 27 (3.9%, HTS group); median ALT and aspartate transaminase levels in the HTS group were 57 U/L (interquartile range 49-80 U/L) and 67 U/L (interquartile range 53-85 U/L), respectively. Younger age, malabsorption symptoms, and low hemoglobin or ferritin were significantly more common in the HTS group at univariate analysis. At multivariate analysis, only age ≤4.27 years correlated with risk of liver involvement (odds ratio 3.73; 95% confidence interval: 1.61-8.66). When retested on a gluten-free diet, all but 3 patients normalized ALT levels; of these, 1 was diagnosed with sclerosing cholangitis. CONCLUSIONS: Liver involvement in celiac children is now less frequent than previously reported, possibly due to changing CD epidemiology. Younger age is the only risk factor. Associated autoimmune liver disease is rare.

First urinary tract infections in children: the role of the risk factors proposed by the Italian recommendations. - Alberici, I; La Manna, A; Pennesi, M; Starc, M; Scozzola, F; Nicolini, G; Toffolo, A; Marra, G; Chimenz, R; Sica, F; Maringhini, S; Monasta, L; et al. (Acta Paediatr, 2019)
AIM: In 2009, the Italian society for paediatric nephrology suggested the need for cystography, following a first febrile urinary tract infection (UTI), only in children at high risk for dilating vesicoureteral reflux or in the event of a second infection. The aim of this study was to evaluate the adequacy of the risk factors proposed by the Italian guidelines. METHODS: Children aged 2-36 months, managed by 10 Italian hospitals between 2009 and 2013, with a first febrile UTI were retrospectively evaluated. RESULTS: Four hundred and fourteen children were included: 51% female, mean age eight months. Escherichia coli was responsible of 84% UTIs. 269 children (65%) presented at least one risk factor, thus were further investigated: 44% had a reflux. The presence of a pathogen other than E. coli significantly predicted high-grade reflux, both in the univariate (Odd Ratio 2.52, 95% Confidence Interval 1.32-4.81, p < 0.005) and multivariate analysis (OR 2.74, 95% CI: 1.39-5.41, p: 0.003). 26/145 children (18%) with no risk factors experienced a second UTI, which prompted the execution of cystography, showing a dilating reflux in 11. CONCLUSION: Among the risk factors proposed by the Italian guidelines, only the presence of a pathogen other than E. coli significantly predicted reflux. Cystography can be postponed in children with no risk factors.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

Management of endometrial, ovarian and cervical cancer in the elderly: current approach to a challenging condition. - Vitale, Salvatore Giovanni; Capriglione, Stella; Zito, Gabriella; Lopez, Salvatore; Gulino, Ferdinando Antonio; Di Guardo, Federica; Vitagliano, Amerigo; Noventa, Marco; La Rosa, Valentina Lucia; Sapia, Fabrizio; Valenti, Gaetano; Rapisarda, Agnese Maria Chiara; et al. (Arch Gynecol Obstet, 2019)
PURPOSE: Gynaecological cancer management in older people represents a current challenge. Therefore, in the present paper, we aimed to gather all the evidence reported in the literature concerning gynecological cancers in the elderly, illustrating the state of art and the future perspectives. METHODS: We searched MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials, IBECS, BIOSIS, Web of Science, SCOPUS and Grey literature (Google Scholar; British Library) from January 1952 to May 2017, using the terms "ovarian cancer", "endometrial cancer", "cervical cancer", "gynecological cancers" combined with 'elderly', 'cancer', 'clinical trial' and 'geriatric assessment'. RESULTS: The search identified 81 citations, of which 65 were potentially relevant after initial evaluation and met the criteria for inclusion and were analyzed. We divided all included studies into three different issue: "Endometrial cancer", "Ovarian cancer" and "Cervical cancer". CONCLUSIONS: The present literature review shows that, in spite of the higher burden of comorbidities, elderly patients can also benefit from standard treatment to manage their gynecological cancers. It is important to overcome the common habit of undertreating the elderly patients because they are more fragile and with a lower life expectancy than their younger counterpart. Further trials with elderly women are warranted.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult-onset cerebellar ataxia in Italy. - Mancini, C; Giorgio, E; Rubegni, A; Pradotto, L; Bagnoli, S; Rubino, E; Prontera, P; Cavalieri, S; Di Gregorio, E; Ferrero, M; Pozzi, E; Riberi, E; et al. (Eur J Neurol, 2019)
BACKGROUND AND PURPOSE: Hereditary ataxias are heterogeneous groups of neurodegenerative disorders, characterized by cerebellar syndromes associated with dysarthria, oculomotor and corticospinal signs, neuropathy and cognitive impairment. Recent reports have suggested mutations in the SPG7 gene, causing the most common form of autosomal recessive spastic paraplegia (MIM#607259), as a main cause of ataxias. The majority of described patients were homozygotes or compound heterozygotes for the c.1529C>T (p.Ala510Val) change. We screened a cohort of 895 Italian patients with ataxia for p.Ala510Val in order to define the prevalence and genotype-phenotype correlation of this variant. METHODS: We set up a rapid assay for c.1529C>T using restriction enzyme analysis after polymerase chain reaction amplification. We confirmed the diagnosis with Sanger sequencing. RESULTS: We identified eight homozygotes and 13 compound heterozygotes, including two novel variants affecting splicing. Mutated patients showed a pure cerebellar ataxia at onset, evolving in mild spastic ataxia (alternatively) associated with dysarthria (~80% of patients), urinary urgency (~30%) and pyramidal signs (~70%). Comparing homozygotes and compound heterozygotes, we noted a difference in age at onset and Scale for the Assessment and Rating of Ataxia score between the two groups, supporting an earlier and more severe phenotype in compound heterozygotes versus homozygotes. CONCLUSIONS: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

ACTN1 mutations lead to a benign form of platelet macrocytosis not always associated with thrombocytopenia. - Faleschini, Michela; Melazzini, Federica; Marconi, Caterina; Giangregorio, Tania; Pippucci, Tommaso; Cigalini, Elena; Pecci, Alessandro; Bottega, Roberta; Ramenghi, Ugo; Siitonen, Timo; Seri, Marco; Pastore, Annalisa; et al. (Br J Haematol, 2018)
The inherited thrombocytopenias (IT) are a heterogeneous group of diseases resulting from mutations in more than 30 different genes. Among them, ACTN1-related thrombocytopenia (ACTN1-RT; Online Mendelian Inheritance in Man: 615193) is one of the most recently identified forms. It has been described as a mild autosomal dominant macrothrombocytopenia caused by mutations in ACTN1, a gene encoding for one of the two non-muscle isoforms of α-actinin. We recently identified seven new unrelated families with ACTN1-RT caused by different mutations. Two of them are novel missense variants (p.Trp128Cys and p.Pro233Leu), whose pathogenic role has been confirmed by in vitro studies. Together with the 10 families we have previously described, our cohort of ACTN1-RT now consists of 49 individuals carrying ACTN1 mutations. This is the largest case series ever collected and enabled a critical evaluation of the clinical aspects of the disease. We concluded that ACTN1-RT is the fourth most frequent form of IT worldwide and it is characterized by platelet macrocytosis in all affected subjects and mild thrombocytopenia in less than 80% of cases. The risk of bleeding, either spontaneous or upon haemostatic challenge, is negligible and there are no other associated defects, either congenital or acquired. Therefore, ACTN1-RT is a benign form of IT, whose diagnosis provides affected individuals and their families with a good prognosis.

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Benign hereditary chorea and deletions outside NKX2-1: What's the role of MBIP? - Invernizzi, Federica; Zorzi, Giovanna; Legati, Andrea; Coppola, Giovanni; d'Adamo, Pio; Nardocci, Nardo; Garavaglia, Barbara; Ghezzi, Daniele (Eur J Med Genet, 2018)
Heterozygous point mutations or deletions of the NKX2-1 gene cause benign hereditary chorea (BHC) or a various combinations of primary hypothyroidism, respiratory distress and neurological disorders. Deletions proximal to, but not encompassing, NKX2-1 have been described in few subjects with brain-lung-thyroid syndrome. We report on a three-generation Italian family, with 6 subjects presenting BHC and harboring a genomic deletion adjacent to NKX2-1 and including the gene MBIP, recently proposed to be relevant for the pathogenesis of brain-lung-thyroid syndrome. We observed a clear reduction of NKX2-1 transcript levels in fibroblasts from our patients compared to controls; this finding suggests that MBIP deletion affects NKX2-1 expression, mimicking haploinsufficiency caused by classical NKX2-1 related mutations.
Keywords: Cells, Cultured; Chorea; Haploinsufficiency; Humans; Intracellular Signaling Peptides and Proteins; Pedigree; Sequence Deletion; Thyroid Nuclear Factor 1

A Child with Diminished Linear Growth and Waddling Gait. - Tamaro, Gianluca; Pederiva, Federica; Dibello, Daniela; Gregori, Massimo; Carbone, Marco; Pantaleoni, Francesca; Dentici, Maria Lisa; Niceta, Marcello; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abnormalities, Multiple; Child; Dwarfism; Female; Gait; Humans; Osteochondrodysplasias; Radiography

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study identifies an association between variants in EFCAB4B gene and periodontal disease in an Italian isolated population. - Bevilacqua, Lorenzo; Navarra, Chiara O; Pirastu, Nicola; Lenarda, Roberto Di; Gasparini, Paolo; Robino, Antonietta (J Periodontal Res, 2018)
BACKGROUND AND OBJECTIVE: Periodontitis in one of the most prevalent dental diseases. Despite numerous studies have investigated its aetiopathogenetic factors, few works have focused on its genetic predisposition and most of them took into account only candidate genes. Therefore, we conducted a Genome Wide Association Study in an Italian isolated population aimed at uncovering genetic variants that predispose to this disorder. METHODS: Diagnosis of chronic periodontitis was made following the criteria of the American Academy of Periodontology. Patients with chronic periodontitis were grouped into different categories: slight, severe, localized and generalized. A control group composed by people without signs of periodontitis or gingivitis was defined. DNA was genotyped using 370k Illumina chips. Linear mixed model regression was used to test the association between each single nucleotide polymorphism (SNP) (independent variable) and the periodontitis status (dependent variable), controlling for confounders sex, age and smoking. The genomic kinship matrix was also used as random effect. RESULTS: Four SNPs on the gene EFCAB4B resulted significantly associated to localized periodontitis (P < 5 × 10 ), with the best hit on the rs242016 SNP (P = 1.5 × 10 ). CONCLUSION: We have identified a novel significant association between the EFCAB4B gene and localized periodontitis. These results open a new perspective in the understanding of genetic factors contributing to this common disorder.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Calcium-Binding Proteins; Chronic Periodontitis; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Young Adult

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

Hypomorphic FANCA mutations correlate with mild mitochondrial and clinical phenotype in Fanconi anemia. - Bottega, Roberta; Nicchia, Elena; Cappelli, Enrico; Ravera, Silvia; De Rocco, Daniela; Faleschini, Michela; Corsolini, Fabio; Pierri, Filomena; Calvillo, Michaela; Russo, Giovanna; Casazza, Gabriella; Ramenghi, Ugo; et al. (Haematologica, 2018)
Fanconi anemia is a rare disease characterized by congenital malformations, aplastic anemia, and predisposition to cancer. Despite the consolidated role of the Fanconi anemia proteins in DNA repair, their involvement in mitochondrial function is emerging. The purpose of this work was to assess whether the mitochondrial phenotype, independent of genomic integrity, could correlate with patient phenotype. We evaluated mitochondrial and clinical features of 11 affected individuals homozygous or compound heterozygous for p.His913Pro and p.Arg951Gln/Trp, the two residues of FANCA that are more frequently affected in our cohort of patients. Although p.His913Pro and p.Arg951Gln proteins are stably expressed in cytoplasm, they are unable to migrate in the nucleus, preventing cells from repairing DNA. In these cells, the electron transfer between respiring complex I-III is reduced and the ATP/AMP ratio is impaired with defective ATP production and AMP accumulation. These activities are intermediate between those observed in wild-type and FANCA-/- cells, suggesting that the variants at residues His913 and Arg951 are hypomorphic mutations. Consistent with these findings, the clinical phenotype of most of the patients carrying these mutations is mild. These data further support the recent finding that the Fanconi anemia proteins play a role in mitochondria, and open up possibilities for genotype/phenotype studies based on novel mitochondrial criteria.

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

Investigation of the link between PROP taste perception and vegetables consumption using FAOSTAT data. - Mezzavilla, Massimo; Notarangelo, Michela; Concas, Maria Pina; Catamo, Eulalia; Gasparini, Paolo; Grillotti, Maria Gemma; Robino, Antonietta (Int J Food Sci Nutr, 2018)
In this work we investigated, in populations located in Central Asia, the relationship between PROP taste perception and vegetables liking and consumption using FAOSTAT dataset. Collected data were analysed using distance matrices, Mantel test and Pearson correlation. Populations showing similar ability in tasting PROP bitterness are more similar as respect to vegetable consumption (r = 0.63, p-value = .05). Moreover, a significant negative correlation was found between the percentage of Non Taster (NT) in different countries and the percentage of vegetable consumption (r = -0.87, p-value = .02), while a significant positive correlation emerged between the percentage of Super Taster (ST) and the percentage of vegetable liking (r = 0.87, p-value = .02). In our work we showed that differences in bitter perception among populations contributes to differences in vegetable liking and vegetable consumption. More in detail, populations with higher percentage of ST consume more vegetables than population where the majority of individuals are NT.

Irinotecan-induced muscular contractions. - Naviglio, Samuele; Rabusin, Marco (Pediatr Blood Cancer, 2018)

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Long term outcome of eight patients with type 1 Leukocyte Adhesion Deficiency (LAD-1): Not only infections, but high risk of autoimmune complications. - De Rose, Domenico Umberto; Giliani, Silvia; Notarangelo, Lucia Dora; Lougaris, Vassilios; Lanfranchi, Arnalda; Moratto, Daniele; Martire, Baldassarre; Specchia, Fernando; Tommasini, Alberto; Plebani, Alessandro; Badolato, Raffaele (Clin Immunol, 2018)
Leukocyte Adhesion Deficiency type 1 (LAD-1) is a rare primary immunodeficiency due to mutations in the gene encoding for the common β-chain of the β2 integrin family (CD18). Herein, we describe clinical manifestations and long-term complications of eight LAD-1 patients. Four LAD-1 patients were treated with hematopoietic stem cell transplantation (HSCT), while the remaining four, including two with moderate LAD-1 deficiency, received continuous antibiotic prophylaxis. Untreated patients presented numerous infections and autoimmune manifestations. In particular, two of them developed renal and intestinal autoimmune diseases, despite the expression of Beta-2 integrin was partially conserved. Other two LAD-1 patients developed type 1 diabetes and autoimmune cytopenia after HSCT, suggesting that HSCT is effective for preventing infections in LAD-1, but does not prevent the risk of the autoimmune complications.

Low-dose sirolimus in two cousins with autoimmune lymphoproliferative syndrome-associated infection. - Nocerino, Agostino; Valencic, Erica; Loganes, Claudia; Pelos, Giorgio; Tommasini, Alberto (Pediatr Int, 2018)
Keywords: Anti-Bacterial Agents; Autoimmune Lymphoproliferative Syndrome; Child; Child, Preschool; Dose-Response Relationship, Drug; Female; Humans; Immunosuppressive Agents; Infant; Male; Otitis Media; Pneumonia, Bacterial; Sirolimus

A new form of inherited thrombocytopenia due to monoallelic loss of function mutation in the thrombopoietin gene. - Noris, Patrizia; Marconi, Caterina; De Rocco, Daniela; Melazzini, Federica; Pippucci, Tommaso; Loffredo, Giuseppe; Giangregorio, Tania; Pecci, Alessandro; Seri, Marco; Savoia, Anna (Br J Haematol, 2018)

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Ocular Manifestations of Paediatric Inflammatory Bowel Disease: A Systematic Review and Meta-analysis. - Ottaviano, Giorgio; Salvatore, Silvia; Salvatoni, Alessandro; Martelossi, Stefano; Ventura, Alessandro; Naviglio, Samuele (J Crohns Colitis, 2018)
Background and Aims: Ocular extraintestinal manifestations [O-EIMs] are known complications of Crohn's disease [CD], ulcerative colitis [UC], and inflammatory bowel disease unclassified [IBD-U]. However, data on their prevalence in children are scarce and there are no clear recommendations on what follow-up should be offered. We aimed to review available data on O-EIMs in children. Methods: In January 2018, we performed a systematic review of published English literature using PubMed and EMBASE databases and disease-specific queries. Results: Fifteen studies [7467 patients] reported data on O-EIMs prevalence in children. Overall prevalence of O-EIMs was 0.62-1.82%. Uveitis was the most common O-EIM. Meta-analysis showed that children with CD are at increased risk of O-EIMs as compared with children with UC and IBD-U (odds ratio [OR] 2.70, 95% confidence interval [CI] 1.51-4.83). Five studies [357 patients] reported data on ophthalmological screening in asymptomatic children: mild asymptomatic uveitis was identified in a variable proportion of patients [1.06-23.1%], more frequently in male patients with CD and colonic involvement. No evidence of ocular complications from untreated uveitis was detected. A total of 23 case reports [24 patients] were identified. Conclusions: Data on O-EIMs in children are scarce. Prevalence of O-EIMs is lower than in adults but may be underestimated because of the possibility of asymptomatic uveitis; however, the long-term significance of this condition is unknown. Children with CD may be at increased risk of O-EIMs. No recommendations on routine ophthalmological examination can be made, but a low threshold for ophthalmological referral should be maintained. Larger studies in paediatric IBD populations are needed.
Keywords: Adolescent; Cataract; Child; Child, Preschool; Colitis, Ulcerative; Crohn Disease; Eye Diseases; Humans; Prevalence; Uveitis

Paediatric Home Artificial Nutrition in Italy: Report from 2016 Survey on Behalf of Artificial Nutrition Network of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP). - Lezo, Antonella; Capriati, Teresa; Spagnuolo, Maria Immacolata; Lacitignola, Laura; Goreva, Irina; Di Leo, Grazia; Cecchi, Nicola; Gandullia, Paolo; Amarri, Sergio; Forchielli, Maria Luisa; Dipasquale, Valeria; Parma, Barbara; et al. (Nutrients, 2018)
Home Artificial Nutrition (HAN) is a safe and efficacious technique that insures children's reintegration into the family, society and school. Epidemiological data on paediatric HAN in Italy are not available. AIM: to detect the prevalence and incidence of Home Parenteral Nutrition (HPN) and Home Enteral Nutrition (HEN), either via tube or mouth, in Italy in 2016. MATERIALS AND METHODS: a specific form was sent to all registered SIGENP members and investigators of local HAN centres, inviting them to provide the requested centre's data and demographics, underlying diseases and HAN characteristics of the patients. RESULTS: we recorded 3403 Italian patients on HAN aged 0 to 19 years from 22 centres: 2277 HEN, 950 Oral Nutritional Supplements (ONS) and 179 HPN programs. The prevalence of HEN (205 pts/million inhabitants) and HPN (16 pts/million inhabitants) has dramatically increased in Italy in the last 9 years. Neurodisabling conditions were the first indication for HEN by tube or mouth while HPN is mainly requested in digestive disorders. CONCLUSIONS: HAN is a widespread and rapidly growing treatment in Italy, as well as in other European countries. Awareness of its extent and characteristics helps improving HAN service and patients' quality of life.
Keywords: Adolescent; Age Factors; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Enteral Nutrition; Female; Health Care Surveys; Home Care Services; Humans; Infant; Infant, Newborn; Italy; Male; Nutritional Status; Parenteral Nutrition, Home; Pediatrics; Time Factors; Young Adult

Pain Intensity and Risk of Bone Fracture in Children With Minor Extremity Injuries. - Zanchi, Chiara; Giangreco, Manuela; Ronfani, Luca; Germani, Claudio; Giorgi, Rita; Calligaris, Lorenzo; Norbedo, Stefania; Liccari, Giulio; Cozzi, Giorgio; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVES: Injuries are one of the most common causes of pediatric emergency department (ED) visit. The aim of this study was to investigate the relationship between the intensity of pain at the ED visit of children presenting with an extremity injury and the risk of fracture. METHODS: We conducted a retrospective study, considering all patients presenting to the ED of a children's hospital in Italy, with an accidental extremity injury, between May and December 2015. We selected all children aged 8 to 17 years who underwent an x-ray. Children with major, multiple, or nonextremity injuries were excluded. Age, sex, spontaneous and palpation pain, local swelling, time between injury, and medical evaluation were recorded. Sensibility and specificity of spontaneous and palpation pain in detecting a fracture were calculated. RESULTS: We reviewed 994 medical records; of these, 344 (34.6%) reported a fracture. Children's median age was 12 years (interquartile range [IQR], 10-14). Median spontaneous pain at the ED visit was not significantly different between children with and without a fracture: 4.0 (1.0-6.0) and 5 (1.0-6.0), respectively (P = 0.129). Children with mild palpation pain and children without an increase of pain of at least 2 points between spontaneous and palpation pain were fractured in 3.2% and 0.97% of cases, respectively. CONCLUSIONS: In this series, pain intensity in children with a minor extremity injury was not a good marker of fracture. Nevertheless, children with mild palpation pain or with a mild increase of pain between spontaneous and palpation pain had a low risk of fracture.

Potential use of MCR-ALS for the identification of coeliac-related biochemical changes in hyperspectral Raman maps from pediatric intestinal biopsies. - Fornasaro, Stefano; Vicario, Annalisa; De Leo, Luigina; Bonifacio, Alois; Not, Tarcisio; Sergo, Valter (Integr Biol (Camb), 2018)
Raman hyperspectral imaging is an emerging practice in biological and biomedical research for label free analysis of tissues and cells. Using this method, both spatial distribution and spectral information of analyzed samples can be obtained. The current study reports the first Raman microspectroscopic characterisation of colon tissues from patients with Coeliac Disease (CD). The aim was to assess if Raman imaging coupled with hyperspectral multivariate image analysis is capable of detecting the alterations in the biochemical composition of intestinal tissues associated with CD. The analytical approach was based on a multi-step methodology: duodenal biopsies from healthy and coeliac patients were measured and processed with Multivariate Curve Resolution Alternating Least Squares (MCR-ALS). Based on the distribution maps and the pure spectra of the image constituents obtained from MCR-ALS, interesting biochemical differences between healthy and coeliac patients has been derived. Noticeably, a reduced distribution of complex lipids in the pericryptic space, and a different distribution and abundance of proteins rich in beta-sheet structures was found in CD patients. The output of the MCR-ALS analysis was then used as a starting point for two clustering algorithms (k-means clustering and hierarchical clustering methods). Both methods converged with similar results providing precise segmentation over multiple Raman images of studied tissues.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Red Flags in Torticollis: A Historical Cohort Study. - Starc, Meta; Norbedo, Stefania; Tubaro, Martina; Ronfani, Luca; Bassanese, Giulia; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: This study aimed to assess the spectrum of pathologies responsible for torticollis in children presenting to the emergency department and to evaluate the associated symptoms to determine clinical red flags for hospitalization. METHODS: This was a historical retrospective cohort study. Medical records of children evaluated in our emergency department for torticollis from 2008 to 2013 were reviewed. RESULTS: Among 392 identified patients, 61% had postural torticollis,19.4% infection related, 16.3% traumatic, and 3.5% other. Twenty-five patients (6.4%) were hospitalized. Four variables were strongly and independently related to the severe outcome: fever, sore throat, headache, and age. CONCLUSIONS: The association of 2 or 3 of these 4 features carried a risk of 32% and 58%, respectively, of having a severe illness.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Emergency Service, Hospital; Female; Hospitalization; Humans; Male; Retrospective Studies; Torticollis

Report on an international workshop on kangaroo mother care: lessons learned and a vision for the future. - Cattaneo, Adriano; Amani, Adidja; Charpak, Nathalie; De Leon-Mendoza, Socorro; Moxon, Sarah; Nimbalkar, Somashekhar; Tamburlini, Giorgio; Villegas, Julieta; Bergh, Anne-Marie (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Globally, complications of prematurity are the leading cause of death in children under five. Preterm infants who survive their first month of life are at greater risk for various diseases and impairments in infancy, childhood and later life, representing a heavy social and economic burden for families, communities and health and social systems. Kangaroo mother care (KMC) is recommended as a beneficial and effective intervention for improving short- and long-term preterm birth outcomes in low- and high-income settings. Nevertheless, KMC is not as widely used as it should be. The International Network on KMC runs biennial workshops and congresses to help improve the coverage and quality of KMC worldwide. This paper reports the results of the two-day workshop held in November 2016, where 92 participants from 33 countries shared experiences in a series of round tables, group work sessions and plenaries. FINDINGS: Barriers to and enablers of KMC are discussed with regard to parents, health workers and the health system. Key factors for effective implementation and uptake relate to appropriate training for health staff, adherence to protocols and the creation of a welcoming environment for families. Recommendations for planning for national programmes are made according to a six-stage change model. Resources and the cost of making progress are discussed in terms of investment, maintenance, and acceleration and scaling-up costs. KMC training requirements are presented according to three levels of care. To ensure quality KMC, key requisites are proposed for the different KMC components and for sensitive communication with caregivers. The group attending to the monitoring and evaluation of KMC at a national and subnational level highlight the lack of standard indicator definitions. Key priorities for investment include health services research, harmonisation of indicators, development of a costing tool, programming and scaling up, and the follow-up of preterm infants. CONCLUSION: It is hoped that this report will help to further scale-up and sustain KMC through a systematic approach that includes raising commitment, identifying key strategies to address the main barriers and using existing facilitators, ensuring training and quality, agreeing on indicators for monitoring and evaluation, and advancing implementation research.
Keywords: Education; Education, Nonprofessional; Female; Government Programs; Health Plan Implementation; Humans; Infant; Infant Mortality; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; International Cooperation; Kangaroo-Mother Care Method; Male

The Role of Oxidative Stress and Membrane Transport Systems during Endometriosis: A Fresh Look at a Busy Corner. - Vitale, Salvatore Giovanni; Capriglione, Stella; Peterlunger, Isabel; La Rosa, Valentina Lucia; Vitagliano, Amerigo; Noventa, Marco; Valenti, Gaetano; Sapia, Fabrizio; Angioli, Roberto; Lopez, Salvatore; Sarpietro, Giuseppe; Rossetti, Diego; et al. (Oxid Med Cell Longev, 2018)
Endometriosis is a condition characterized by the presence of endometrial tissue outside the uterine cavity, leading to a chronic inflammatory reaction. It is one of the most widespread gynecological diseases with a 10-15% prevalence in the general female population, rising up to 30-45% in patients with infertility. Although it was first described in 1860, its etiology and pathogenesis are still unclear. It is now accepted that inflammation plays a central role in the development and progression of endometriosis. In particular, it is marked by an inflammatory process associated with the overproduction of an array of inflammatory mediators such as prostaglandins, metalloproteinases, cytokines, and chemokines. In addition, the growth and adhesion of endometrial cells in the peritoneal cavity due to reactive oxygen species (ROS) and free radicals lead to disease onset, its ensuing symptoms-among which pain and infertility. The aim of our review is to evaluate the role of oxidative stress and ROS in the pathogenesis of endometriosis and the efficacy of antioxidant therapy in the treatment and mitigation of its symptoms.
Keywords: Endometriosis; Female; Humans; Oxidative Stress

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

Acute Abdominal Pain: Recognition and Management of Constipation in the Emergency Department. - Norbedo, Stefania; Bassanese, Giulia; Barbieri, Francesca; Barbi, Egidio (Pediatr Emerg Care, 2017)
OBJECTIVE: The main aim of the study was to investigate the incidence and the clinically relevant features of functional constipation in patients evaluated for acute abdominal pain in a tertiary care pediatric emergency department. METHODS: This is a retrospective study. We analyzed 4394 medical records and recorded the information (demographics, triage code, symptoms, medical history, physical evaluation, laboratory tests, radiological studies, procedures, and treatments) of all patients admitted for acute abdominal pain to the emergency department of the IRCCS Burlo Garofolo, Trieste, during 2010 to 2013. RESULTS: In this study, a quarter of patients (1020) presenting in the emergency department with acute abdominal pain were affected by functional constipation. Acute pain associated with functional constipation is generally rated from moderate to severe, and the location of the pain on physical evaluation was not a sufficient criterion to guide diagnosis. Isolated vomiting may be present in a minority of cases. Digital rectal exploration was never performed; the majority of patients were treated by means of an enema with prompt relief. Six percent of patients with constipation underwent radiological studies. CONCLUSIONS: This study confirms that the medical history provides a pivotal role in the diagnosis of functional constipation. Digital rectal exploration and x-rays should be avoided in this setting, whereas an enema plays a useful diagnostic and therapeutic role in our study patients.
Keywords: Abdominal Pain; Acute Pain; Adolescent; Child; Child, Preschool; Constipation; Emergency Service, Hospital; Enema; Female; Humans; Incidence; Infant; Male; Retrospective Studies

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Authors' Reply to M.S. Raghuraman: "Intranasal Dexmedetomidine for Procedural Sedation in Children, a Suitable Alternative to Chloral Hydrate". - Cozzi, Giorgio; Norbedo, Stefania; Barbi, Egidio (Paediatr Drugs, 2017)
Keywords: Administration, Intranasal; Child; Chloral Hydrate; Dexmedetomidine; Humans; Hypnotics and Sedatives; Infant

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Bilateral Finger Swelling in an Adolescent. - Naviglio, Samuele; Mazzolai, Michele; Ventura, Alessandro (J Pediatr, 2017)

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations. - Xue, Yali; Mezzavilla, Massimo; Haber, Marc; McCarthy, Shane; Chen, Yuan; Narasimhan, Vagheesh; Gilly, Arthur; Ayub, Qasim; Colonna, Vincenza; Southam, Lorraine; Finan, Christopher; Massaia, Andrea; et al. (Nat Commun, 2017)
The genetic features of isolated populations can boost power in complex-trait association studies, and an in-depth understanding of how their genetic variation has been shaped by their demographic history can help leverage these advantageous characteristics. Here, we perform a comprehensive investigation using 3,059 newly generated low-depth whole-genome sequences from eight European isolates and two matched general populations, together with published data from the 1000 Genomes Project and UK10K. Sequencing data give deeper and richer insights into population demography and genetic characteristics than genotype-chip data, distinguishing related populations more effectively and allowing their functional variants to be studied more fully. We demonstrate relaxation of purifying selection in the isolates, leading to enrichment of rare and low-frequency functional variants, using novel statistics, DVxy and SVxy. We also develop an isolation-index (Isx) that predicts the overall level of such key genetic characteristics and can thus help guide population choice in future complex-trait association studies.
Keywords: European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

First-time success with needle procedures was higher with a warm lidocaine and tetracaine patch than an eutectic mixture of lidocaine and prilocaine cream. - Cozzi, Giorgio; Borrometi, Fabio; Benini, Franca; Neri, Elena; Rusalen, Francesca; Celentano, Loredana; Zanon, Davide; Schreiber, Silvana; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2017)
AIM: More than 50% of children report apian during venepuncture or intravenous cannulation and using local anaesthetics before needle procedures can lead to different success rates. This study examined how many needle procedures were successful at the first attempt when children received either a warm lidocaine and tetracaine patch or an eutectic mixture of lidocaine and prilocaine (EMLA) cream. METHODS: We conducted this multicentre randomised controlled trial at three tertiary-level children's hospitals in Italy in 2015. Children aged three to 10 years were enrolled in an emergency department, paediatric day hospital and paediatric ward and randomly allocated to receive a warm lidocaine and tetracaine patch or EMLA cream. The primary outcome was the success rate at the first attempt. RESULTS: The analysis included 172 children who received a warm lidocaine and tetracaine patch and 167 who received an EMLA cream. The needle procedure was successful at the first attempt in 158 children (92.4%) who received the warm patch and in 142 children (85.0%) who received the cream (p = 0.03). The pain scores were similar in both groups. CONCLUSION: This study showed that the first-time needle procedure success was 7.4% higher in children receiving a warm lidocaine and tetracaine patch than EMLA cream.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Phlebotomy; Prilocaine; Tetracaine

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Gray platelet syndrome: Novel mutations of the NBEAL2 gene. - Bottega, Roberta; Nicchia, Elena; Alfano, Caterina; Glembotsky, Ana C; Pastore, Annalisa; Bertaggia-Calderara, Debora; Bisig, Bettina; Duchosal, Michel A; Arbesú, Guillermo; Alberio, Lorenzo; Heller, Paula G; Savoia, Anna (Am J Hematol, 2017)
Keywords: Adult; Alleles; Blood Proteins; Child; Female; Gene Expression; Gene Frequency; Genotype; Gray Platelet Syndrome; Humans; Male; Mutation; Phenotype; Platelet Aggregation; Platelet Count; Platelet Membrane Glycoproteins

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the ureteropelvic-junction obstruction. - Chiarenza, Salvatore Fabio; Bleve, Cosimo; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; Bagolan, Pietro; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Humans; Infant; Kidney Pelvis; Minimally Invasive Surgical Procedures; Ureteral Obstruction; Video-Assisted Surgery

Immediate delivery or expectant management in gestational diabetes at term: the GINEXMAL randomised controlled trial. - Alberico, S; Erenbourg, A; Hod, M; Yogev, Y; Hadar, E; Neri, F; Ronfani, L; Maso, G (BJOG, 2017)
OBJECTIVE: To evaluate maternal and perinatal outcomes after induction of labour versus expectant management in pregnant women with gestational diabetes at term. DESIGN: Multicentre open-label randomised controlled trial. SETTING: Eight teaching hospitals in Italy, Slovenia, and Israel. SAMPLE: Singleton pregnancy, diagnosed with gestational diabetes by the International Association of Diabetes and Pregnancy Study Groups criteria (IADPSGC), between 38 and 39 weeks of gestation, without other maternal or fetal conditions. METHODS: Patients were randomly assigned to induction of labour or expectant management and intensive follow-up. Data were analysed by 'intention to treat'. MAIN OUTCOME MEASURES: The primary outcome was incidence of caesarean section. Secondary outcomes were maternal and perinatal mortality and morbidity. RESULTS: A total of 425 women were randomised to the study groups. The incidence of caesarean section was 12.6% in the induction group versus 11.7% in the expectant group. No difference was found between the two groups (relative risk, RR 1.06; 95% confidence interval, 95% CI 0.64-1.77; P = 0.81). The incidence of non-spontaneous delivery, either by caesarean section or by operative vaginal delivery, was 21.0 and 22.3%, respectively (RR 0.94; 95% CI 0.66-1.36; P = 0.76). Neither maternal nor fetal deaths occurred. The few cases of shoulder dystocia were solved without any significant birth trauma. CONCLUSIONS: In women with gestational diabetes, without other maternal or fetal conditions, no difference was detected in birth outcomes regardless of the approach used (i.e. active versus expectant management). Although the study was underpowered, the magnitude of the between-group difference was very small and without clinical relevance. TWEETABLE ABSTRACT: Immediate delivery or expectant management in gestational diabetes at term?
Keywords: Adult; Delivery, Obstetric; Diabetes, Gestational; Female; Humans; Infant, Newborn; Israel; Italy; Maternal Mortality; Perinatal Mortality; Pregnancy; Pregnancy Outcome; Slovenia; Term Birth; Watchful Waiting

Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Clinical and Hypoxemic Childhood Pneumonia over Three Years in Central Malawi: An Observational Study. - McCollum, Eric D; Nambiar, Bejoy; Deula, Rashid; Zadutsa, Beatiwel; Bondo, Austin; King, Carina; Beard, James; Liyaya, Harry; Mankhambo, Limangeni; Lazzerini, Marzia; Makwenda, Charles; Masache, Gibson; et al. (PLoS One, 2017)
BACKGROUND: The pneumococcal conjugate vaccine's (PCV) impact on childhood pneumonia during programmatic conditions in Africa is poorly understood. Following PCV13 introduction in Malawi in November 2011, we evaluated the case burden and rates of childhood pneumonia. METHODS AND FINDINGS: Between January 1, 2012-June 30, 2014 we conducted active pneumonia surveillance in children <5 years at seven hospitals, 18 health centres, and with 38 community health workers in two districts, central Malawi. Eligible children had clinical pneumonia per Malawi guidelines, defined as fast breathing only, chest indrawing +/- fast breathing, or, ≥1 clinical danger sign. Since pulse oximetry was not in the Malawi guidelines, oxygenation <90% defined hypoxemic pneumonia, a distinct category from clinical pneumonia. We quantified the pneumonia case burden and rates in two ways. We compared the period immediately following vaccine introduction (early) to the period with >75% three-dose PCV13 coverage (post). We also used multivariable time-series regression, adjusting for autocorrelation and exploring seasonal variation and alternative model specifications in sensitivity analyses. The early versus post analysis showed an increase in cases and rates of total, fast breathing, and indrawing pneumonia and a decrease in danger sign and hypoxemic pneumonia, and pneumonia mortality. At 76% three-dose PCV13 coverage, versus 0%, the time-series model showed a non-significant increase in total cases (+47%, 95% CI: -13%, +149%, p = 0.154); fast breathing cases increased 135% (+39%, +297%, p = 0.001), however, hypoxemia fell 47% (-5%, -70%, p = 0.031) and hospital deaths decreased 36% (-1%, -58%, p = 0.047) in children <5 years. We observed a shift towards disease without danger signs, as the proportion of cases with danger signs decreased by 65% (-46%, -77%, p<0.0001). These results were generally robust to plausible alternative model specifications. CONCLUSIONS: Thirty months after PCV13 introduction in Malawi, the health system burden and rates of the severest forms of childhood pneumonia, including hypoxemia and death, have markedly decreased.
Keywords: Child; Child Mortality; Cost of Illness; Dose-Response Relationship, Immunologic; Geography; Humans; Hypoxia; Malawi; Pneumococcal Vaccines; Pneumonia, Pneumococcal; Time Factors; Vaccines, Conjugate

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Improving the quality of hospital care for children by supportive supervision: a cluster randomized trial, Kyrgyzstan. - Lazzerini, Marzia; Shukurova, Venera; Davletbaeva, Marina; Monolbaev, Kubanychbek; Kulichenko, Tatiana; Akoev, Yuri; Bakradze, Maya; Margieva, Tea; Mityushino, Ilya; Namazova-Baranova, Leyla; Boronbayeva, Elnura; Kuttumuratova, Aigul; et al. (Bull World Health Organ, 2017)
OBJECTIVE: To determine whether periodic supportive supervision after a training course improved the quality of paediatric hospital care in Kyrgyzstan, where inappropriate care was common but in-hospital postnatal mortality was low. METHODS: In a cluster, randomized, parallel-group trial, 10 public hospitals were allocated to a 4-day World Health Organization (WHO) course on hospital care for children followed by periodic supportive supervision by paediatricians for 1 year, while 10 hospitals had no intervention. We assessed prospectively 10 key indicators of inappropriate paediatric case management, as indicated by WHO guidelines. The primary indicator was the combination of the three indicators: unnecessary hospitalization, increased iatrogenic risk and unnecessary painful procedures. An independent team evaluated the overall quality of care. FINDINGS: We prospectively reviewed the medical records of 4626 hospitalized children aged 2 to 60 months. In the intervention hospitals, the mean proportion of the primary indicator decreased from 46.9% (95% confidence interval, CI: 24.2 to 68.9) at baseline to 6.8% (95% CI: 1.1 to 12.1) at 1 year, but was unchanged in the control group (45.5%, 95% CI: 25.2 to 67.9, to 64.7%, 95% CI: 43.3 to 86.1). At 1 year, the risk ratio for the primary indicator in the intervention versus the control group was 0.09 (95% CI: 0.06 to 0.13). The proportions of the other nine indicators also decreased in the intervention group ( < 0.0001 for all). Overall quality of care improved significantly in intervention hospitals. CONCLUSION: Periodic supportive supervision for 1 year after a training course improved both adherence to WHO guidelines on hospital care for children and the overall quality of paediatric care.
Keywords: Child; Child Care; Cluster Analysis; Hospitalization; Hospitals, Public; Humans; Kyrgyzstan; Medical Audit; Pediatricians; Professional Role; Prospective Studies; Quality Improvement

Intranasal Dexmedetomidine for Procedural Sedation in Children, a Suitable Alternative to Chloral Hydrate. - Cozzi, Giorgio; Norbedo, Stefania; Barbi, Egidio (Paediatr Drugs, 2017)
Sedation is often required for children undergoing diagnostic procedures. Chloral hydrate has been one of the sedative drugs most used in children over the last 3 decades, with supporting evidence for its efficacy and safety. Recently, chloral hydrate was banned in Italy and France, in consideration of evidence of its carcinogenicity and genotoxicity. Dexmedetomidine is a sedative with unique properties that has been increasingly used for procedural sedation in children. Several studies demonstrated its efficacy and safety for sedation in non-painful diagnostic procedures. Dexmedetomidine's impact on respiratory drive and airway patency and tone is much less when compared to the majority of other sedative agents. Administration via the intranasal route allows satisfactory procedural success rates. Studies that specifically compared intranasal dexmedetomidine and chloral hydrate for children undergoing non-painful procedures showed that dexmedetomidine was as effective as and safer than chloral hydrate. For these reasons, we suggest that intranasal dexmedetomidine could be a suitable alternative to chloral hydrate.
Keywords: Administration, Intranasal; Child; Chloral Hydrate; Dexmedetomidine; Humans; Hypnotics and Sedatives

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

Long-Term Survival After Hematopoietic Stem Cell Transplantation for Complete STAT1 Deficiency. - Naviglio, Samuele; Soncini, Elena; Vairo, Donatella; Lanfranchi, Arnalda; Badolato, Raffaele; Porta, Fulvio (J Clin Immunol, 2017)
PURPOSE: Complete signal transducer and activator of transcription 1 (STAT1) deficiency is a rare autosomal recessive condition characterized by impairment of intracellular signaling from both type I and type II interferons (IFN). Affected patients are prone to early severe mycobacterial and viral infections, which usually result in death before 18 months of age. We previously reported a patient affected by complete STAT1 deficiency who underwent hematopoietic stem cell transplantation (HSCT). Here, we describe the transplantation procedures and long-term outcomes. METHODS: The patient, who had suffered multiple life-threatening mycobacterial and viral infections in the first years of life, underwent HSCT at 4 years of age from a partially matched (HLA compatibility 8/10) unrelated donor after a myeloablative conditioning regimen consisting of busulfan, cyclophosphamide, and anti-thymocyte globulin. RESULTS: Hematological reconstitution was detected at d+15, with full donor engraftment demonstrated by molecular analysis of leukocytes. Several complications occurred in the post-transplantation phase, including acute graft versus host disease, posterior reversible encephalopathy, thrombotic thrombocytopenic purpura, bilateral keratoconjunctivitis with complete loss of vision, and chronic lower limb lymphedema. Analysis of STAT1 in CD3 cells at 90 and 120 days after HSCT by flow cytometry showed normal STAT1 phosphorylation levels in response to IFN-α. CONCLUSIONS: Notably, no severe infections occurred after discharge (day + 90) during a 9-year follow-up, suggesting that normal response to IFNs in hematopoietic cells is sufficient to provide protection in humans.
Keywords: Child, Preschool; Hematopoietic Stem Cell Transplantation; Humans; Immunologic Deficiency Syndromes; Male; STAT1 Transcription Factor; Treatment Outcome

LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development. - Zupin, L; Robino, A; Navarra, C O; Pirastu, N; Di Lenarda, R; Gasparini, P; Crovella, S; Bevilacqua, L (Oral Dis, 2017)
OBJECTIVES: Chronic periodontitis is a common pathological condition that affects the supporting tissue of the teeth, leading to progressive alveolar bone destruction and teeth loss. The disease is caused by bacteria and derives from an altered host immune and inflammatory response, also involving different factors such as the oral hygiene, smoking, and genetic background. The innate immune response, the first line of host defense, could also play an important role in the susceptibility to chronic periodontitis. In this study, we evaluated the possible association between periodontal disease and seven genetic variations within DEFB1 and LTF genes, encoding for β-defensins 1 and lactoferrin (two members of oral innate immune system), in an Italian isolated population. SUBJECTS AND METHODS: DEFB1 5'UTR g. -52G>A (rs1799946), g. -44C>G (rs1800972), g. -20G>A (rs11362), 3'UTR c*5G>A (rs1047031), c*87A>G (rs1800971), LTF p.Ala29Thr (rs1126477), and p.Lys47Arg (rs1126478) single nucleotide polymorphisms (SNPs) were analyzed in 155 healthy individuals and 439 chronic periodontitis patients from North-East Italy. RESULTS: Significant associations were found between periodontitis and g. -20G>A (rs11362) and g. -44C>G (rs1800972) SNPs in DEFB1 gene as well as p.Ala29Thr (rs1126477) and p.Lys47Arg (rs1126478) SNPs in LTF gene. DISCUSSION: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; beta-Defensins; Case-Control Studies; Chronic Periodontitis; Female; Genetic Predisposition to Disease; Humans; Lactoferrin; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine

Mutations of RUNX1 in families with inherited thrombocytopenia. - De Rocco, Daniela; Melazzini, Federica; Marconi, Caterina; Pecci, Alessandro; Bottega, Roberta; Gnan, Chiara; Palombo, Flavia; Giordano, Paola; Coccioli, Maria Susanna; Glembotsky, Ana C; Heller, Paula G; Seri, Marco; et al. (Am J Hematol, 2017)
Keywords: Adult; Blood Platelets; Cell Size; Child; Child, Preschool; Core Binding Factor Alpha 2 Subunit; Female; Frameshift Mutation; Genes, Dominant; Heterozygote; Humans; Introns; Leukemia, Myeloid, Acute; Male; Middle Aged; Mutation, Missense; Protein Domains; RNA Splice Sites; Sequence Deletion; Thrombocythemia, Essential; Thrombopoietin; Transcriptional Activation; Young Adult

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Ocular Involvement in Children with Inflammatory Bowel Disease. - Naviglio, Samuele; Parentin, Fulvio; Nider, Silvia; Rassu, Nicolò; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2017)
BACKGROUND: Data on ocular manifestations of inflammatory bowel disease (IBD) in children are limited. Some authors have reported a high prevalence of asymptomatic uveitis, yet the significance of these observations is unknown and there are no recommendations on which ophthalmologic follow-up should be offered. METHODS: Children with IBD seen at a single referral center for pediatric gastroenterology were offered ophthalmologic evaluation as part of routine care for their disease. Ophthalmologic evaluation included review of ocular history as well as slit-lamp and fundoscopic examination. Medical records were also reviewed for previous ophthalmologic diagnoses or complaints. RESULTS: Data from 94 children were included (52 boys; median age 13.4 yr). Forty-six patients had a diagnosis of Crohn's disease, 46 ulcerative colitis, and 2 IBD unclassified. Intestinal disease was in clinical remission in 70% of the patients; fecal calprotectin was elevated in 64%. One patient with Crohn's disease had a previous diagnosis of clinically manifest uveitis (overall uveitis prevalence: 1.06%; incidence rate: 0.3 per 100 patient-years). This patient was also the only one who was found to have asymptomatic uveitis at slit-lamp examination. A second patient had posterior subcapsular cataract associated with corticosteroid treatment. No signs of intraocular complications from previous unrecognized uveitis were observed in any patient. CONCLUSIONS: Children with IBD may have asymptomatic uveitis, yet its prevalence seems lower than previously reported, and it was not found in children without a previous diagnosis of clinically manifest uveitis. No ocular complications from prior unrecognized uveitis were observed.
Keywords: Adolescent; Child; Child, Preschool; Feces; Female; Humans; Inflammatory Bowel Diseases; Italy; Leukocyte L1 Antigen Complex; Male; Remission Induction; Uveitis

Phenotypic expression of 19q13.32 microdeletions: Report of a new patient and review of the literature. - Travan, Laura; Naviglio, Samuele; De Cunto, Angela; Pellegrin, Andrea; Pecile, Vanna; Spinelli, Alessandro Mauro; Cappellani, Stefania; Faletra, Flavio (Am J Med Genet A, 2017)
The phenotypic manifestations of microdeletions in the 19q13.32 region are still poorly known. In this paper we report a patient who presented with hypotonia, developmental delay, facial dysmorphism, micrognathia, kyphoscoliosis, and buried penis. Chromosomal microarray revealed an interstitial 327 kb de novo microdeletion in the 19q13.32 region comprising eight genes (ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191). Previously reported cases of microdeletions in the 19q13.32 region were reviewed and compared to our patient, highlighting the common features of a possible 19q13.32 microdeletion syndrome.

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience. - El Hachem, Maya; Gesualdo, Francesco; Diociaiuti, Andrea; Berti, Irene; Vercellino, Nadia; Boccaletti, Valeria; Neri, Iria; Porcedda, Giulio; Greco, Antonella; Carnevale, Claudia; Oranges, Teresa; Cutrone, Mario; et al. (Ital J Pediatr, 2017)
BACKGROUND: Despite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age. METHODS: We retrospectively reviewed the records of patients followed up for IH, on propranolol treatment started before 5 weeks or after 5 months of age, and collected information on sociodemographic data, treatment indications, IH involution, IH relapse, and treatment side effects. RESULTS: A total of 343 patients were enrolled; 15 were started on propranolol before 5 weeks (group 1), 328 were started after 5 months of age (group 2). The most frequent indications were permanent aesthetical disfigurement (91.8%) and function threatening complications (42.6%). In most cases, the treatment was effective. The involution was partial in 67.7% of patients. In 11.8% of cases a relapse was observed. No relapse was observed in group 1. Treatment complications were reported in 15.8% of children, most frequently sleep disorders (6.6%), followed by irritability (5.1%) and diarrhea (2.2%). Only a case of mild constipation was observed in group 1. CONCLUSION: The safety and effectiveness profile of propranolol in infants younger than 5 weeks or older than 5 months may be acceptable. Taking in account propranolol's potential in preventing severe complications, further studies should assess the acceptability of propranolol treatment, especially in the <5-week age group .
Keywords: Administration, Oral; Age Factors; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Hemangioma; Humans; Infant; Infant, Newborn; Italy; Male; Patient Safety; Propranolol; Retrospective Studies; Skin Neoplasms; Treatment Outcome

Somatic symptom disorder was common in children and adolescents attending an emergency department complaining of pain. - Cozzi, Giorgio; Minute, Marta; Skabar, Aldo; Pirrone, Angela; Jaber, Mohamad; Neri, Elena; Montico, Marcella; Ventura, Alessandro; Barbi, Egidio (Acta Paediatr, 2017)
AIM: The aim of this study was to quantify the prevalence of somatic pain in a paediatric emergency department (ED). METHODS: We conducted a prospective observational study using patients admitted to the ED of an Italian children's hospital between December 2014 and February 2015. We enrolled children aged 7-17 who turned up at the ED complaining of pain. Patients and parents were asked to fill in a questionnaire to allow the analysis of the patients' medical history and provide contact details for follow-up. We divided the enrolled patients into four groups: post-traumatic pain, organic pain, functional pain and somatic pain. The questionnaire was used to define pain characteristics and to generate an impairment score. RESULTS: Of the 713 patients who met inclusion criteria, 306 (42.9%) were enrolled in the study. Of these, 135 (44.0%) suffered from post-traumatic pain, 104 (34.0%) from organic pain, 41 (13.4%) from functional pain and 26 (8.6%) from somatic pain. Somatic pain patients had endured pain longer, had missed more school days and had suffered severe functional impairment. CONCLUSION: This study highlighted that somatic pain was a significant contributor to paediatric emergency room visits and should be suspected and diagnosed in children reporting pain.
Keywords: Adolescent; Child; Emergency Service, Hospital; Female; Humans; Italy; Male; Medically Unexplained Symptoms; Pain; Prospective Studies

Targeted sequencing identifies novel variants involved in autosomal recessive hereditary hearing loss in Qatari families. - Alkowari, Moza K; Vozzi, Diego; Bhagat, Shruti; Krishnamoorthy, Navaneethakrishnan; Morgan, Anna; Hayder, Yousra; Logendra, Barathy; Najjar, Nehal; Gandin, Ilaria; Gasparini, Paolo; Badii, Ramin; Girotto, Giorgia; et al. (Mutat Res, 2017)
Hereditary hearing loss is characterized by a very high genetic heterogeneity. In the Qatari population the role of GJB2, the worldwide HHL major player, seems to be quite limited compared to Caucasian populations. In this study we analysed 18 Qatari families affected by non-syndromic hearing loss using a targeted sequencing approach that allowed us to analyse 81 genes simultaneously. Thanks to this approach, 50% of these families (9 out of 18) resulted positive for the presence of likely causative alleles in 6 different genes: CDH23, MYO6, GJB6, OTOF, TMC1 and OTOA. In particular, 4 novel alleles were detected while the remaining ones were already described to be associated to HHL in other ethnic groups. Molecular modelling has been used to further investigate the role of novel alleles identified in CDH23 and TMC1 genes demonstrating their crucial role in Ca2+ binding and therefore possible functional role in proteins. Present study showed that an accurate molecular diagnosis based on next generation sequencing technologies might largely improve molecular diagnostics outcome leading to benefits for both genetic counseling and definition of recurrence risk.
Keywords: Adolescent; Alleles; Cadherins; Child; Child, Preschool; Connexins; Female; GPI-Linked Proteins; Hearing Loss, Sensorineural; Humans; Infant; Male; Membrane Proteins; Models, Molecular; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Qatar; Sequence Analysis, DNA

A Teenager with Sudden Unilateral Breast Enlargement. - Pellegrin, Maria Chiara; Naviglio, Samuele; Cattaruzzi, Elisabetta; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2017)
Keywords: Bullying; Child; Gynecomastia; Hematoma; Humans; Male; Wounds, Nonpenetrating

Towards measles elimination in Italy: Virological surveillance and genotypes trend (2013-2015). - Magurano, Fabio; Baggieri, Melissa; Filia, Antonietta; Del Manso, Martina; Lazzarotto, Tiziana; Amendola, Antonella; D'Agaro, Pierlanfranco; Chironna, Maria; Ansaldi, Filippo; Iannazzo, Stefania; Bucci, Paola; Marchi, Antonella; et al. (Virus Res, 2017)
In accordance with the goal of the World Health Organization Regional Office for Europe, the Italian National Measles and Rubella Elimination Plan aimed to interrupt indigenous measles transmission in Italy by the end of 2015. However, from 2013 to 2015, Italy experienced high measles burden with 4902 measles cases (49.3% laboratory-confirmed) reported to the enhanced measles surveillance system (cumulative incidence in the triennium reference period: 2.4/100,000 population). The measles elimination goal was not reached. Laboratory surveillance of measles circulating genotypes is performed by the Measles and Rubella National Reference Laboratory (NRL) at the Italian National Institute of Health (Istituto Superiore di Sanità - ISS), in Rome. Samples received from 1 January 2013-31 December 2015 were analysed. Those positive for measles genome by molecular tests were sequenced and phylogenetically analysed. Phylogenetic analysis performed by NRL identified that genotypes D4 and D8 were endemic and co-circulated in 2011-2013: study results show that genotype D4 disappeared during 2013. Sporadic cases were associated to genotype B3 during 2011-2013, which became endemic in Italy during 2014 and co-circulated with D8 until 2015. Sporadic cases were found belonging to genotypes D9 and H1 all over the period in exam. Similar trend has been observed in European WHO Region.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Disease Outbreaks; Female; Genotype; Humans; Infant; Italy; Male; Measles; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny; RNA, Viral; Sentinel Surveillance; Young Adult

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Withdrawal Assessment Tool-1 Monitoring in PICU: A Multicenter Study on Iatrogenic Withdrawal Syndrome. - Amigoni, Angela; Mondardini, Maria Cristina; Vittadello, Ilaria; Zaglia, Federico; Rossetti, Emanuele; Vitale, Francesca; Ferrario, Stefania; Savron, Fabio; Coffaro, Giancarlo; Brugnaro, Luca; Amato, Roberta; Wolfler, Andrea; et al. (Pediatr Crit Care Med, 2017)
OBJECTIVES: Withdrawal syndrome is an adverse reaction of analgesic and sedative therapy, with a reported occurrence rate between 17% and 57% in critically ill children. Although some factors related to the development of withdrawal syndrome have been identified, there is weak evidence for the effectiveness of preventive and therapeutic strategies. The main aim of this study was to evaluate the frequency of withdrawal syndrome in Italian PICUs, using a validated instrument. We also analyzed differences in patient characteristics, analgesic and sedative treatment, and patients' outcome between patients with and without withdrawal syndrome. DESIGN: Observational multicenter prospective study. SETTING: Eight Italian PICUs belonging to the national PICU network Italian PICU network. PATIENTS: One hundred thirteen patients, less than 18 years old, mechanically ventilated and treated with analgesic and sedative therapy for five or more days. They were admitted in PICU from November 2012 to May 2014. INTERVENTIONS: Symptoms of withdrawal syndrome were monitored with Withdrawal Assessment Tool-1 scale. MEASUREMENTS AND MAIN RESULTS: The occurrence rate of withdrawal syndrome was 64.6%. The following variables were significantly different between the patients who developed withdrawal syndrome and those who did not: type, duration, and cumulative dose of analgesic therapy; duration and cumulative dose of sedative therapy; clinical team judgment about analgesia and sedation's difficulty; and duration of analgesic weaning, mechanical ventilation, and PICU stay. Multivariate logistic regression analysis revealed that patients receiving morphine as their primary analgesic were 83% less likely to develop withdrawal syndrome than those receiving fentanyl or remifentanil. CONCLUSIONS: Withdrawal syndrome was frequent in PICU patients, and patients with withdrawal syndrome had prolonged hospital treatment. We suggest adopting the lowest effective dose of analgesic and sedative drugs and frequent reevaluation of the need for continued use. Further studies are necessary to define common preventive and therapeutic strategies.
Keywords: Adolescent; Analgesics; Child; Child, Preschool; Critical Care; Female; Humans; Hypnotics and Sedatives; Iatrogenic Disease; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Italy; Logistic Models; Male; Prospective Studies; Respiration, Artificial; Substance Withdrawal Syndrome

A young goalkeeper with buttock pain and fever. - Moressa, Valentina; Pastore, Serena; Naviglio, Samuele; Ventura, Alessandro (BMJ, 2017)
Keywords: Adolescent; Buttocks; Fever; Humans; Male; Musculoskeletal Pain; Pyomyositis

An Animal Model for the Juvenile Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis. - Marin, Veronica; Rosso, Natalia; Dal Ben, Matteo; Raseni, Alan; Boschelle, Manuela; Degrassi, Cristina; Nemeckova, Ivana; Nachtigal, Petr; Avellini, Claudio; Tiribelli, Claudio; Gazzin, Silvia (PLoS One, 2016)
Non Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH) are the hepatic manifestations of the metabolic syndrome; worrisome is the booming increase in pediatric age. To recreate the full spectrum of juvenile liver pathology and investigate the gender impact, male and female C57Bl/6 mice were fed with high fat diet plus fructose in the drinking water (HFHC) immediately after weaning (equal to 3-years old human), and disease progression followed for 16 weeks, until adults (equal to 30-years old human). 100% of subjects of both genders on HFHC diet developed steatosis in 4weeks, and some degree of fibrosis in 8weeks, with the 86% of males and 15% of females presenting a stage 2 fibrosis at 16weeks. Despite a similar final liver damage both groups, a sex difference in the pathology progression was observed. Alterations in glucose homeostasis, dyslipidemia, hepatomegaly and obese phenotype were evident from the very beginning in males with an increased hepatic inflammatory activity. Conversely, such alterations were present in females only at the end of the HFHC diet (with the exception of insulin resistance and the hepatic inflammatory state). Interestingly, only females showed an altered hepatic redox state. This juvenile model appears a good platform to unravel the underlying gender dependent mechanisms in the progression from NAFLD to NASH, and to characterize novel therapeutic approaches.

Association of the HLA-G 3'UTR polymorphisms with colorectal cancer in Italy: a first insight. - Garziera, M; Catamo, E; Crovella, S; Montico, M; Cecchin, E; Lonardi, S; Mini, E; Nobili, S; Romanato, L; Toffoli, G (Int J Immunogenet, 2016)
This study aimed to explore functional and regulatory polymorphisms and haplotypes at the HLA-G 3'UTR region in colorectal cancer development. The presence of nonpolymorphic variants was also evaluated. Three-hundred and eight patients with colorectal cancer and 294 healthy controls were analysed at the germinal level. We found an association with increased risk of colorectal cancer for +2960 14-bp INDEL, +3196 C>G SNPs and UTR-2 haplotype, and a 'protective' role for +3003 T>C, +3010 C>G polymorphisms and UTR-4 haplotype. We detected in 3 distinct patients, a novel nucleotide change (+3037 C>A) and 2 already described rare variants, +3032 G/C (EUR MAF = 0.1%) and +3092 G/T (EUR MAF = 0%). This is the first study showing associations between different polymorphisms in the HLA-G 3'UTR and colorectal cancer susceptibility.

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

Clinical Characteristics of Patients Carrying the Q703K Variant of the NLRP3 Gene: A 10-year Multicentric National Study. - Naselli, Aldo; Penco, Federica; Cantarini, Luca; Insalaco, Antonella; Alessio, Mariolina; Tommasini, Alberto; Maggio, Cristina; Obici, Laura; Gallizi, Romina; Cimmino, Marco; Signa, Sara; Lucherini, Orso Maria; et al. (J Rheumatol, 2016)
OBJECTIVE: The aim of our study was to analyze the clinical and functional effect of the p.Q703K (p. Q705K, c. 2107C>A) variant of the NLRP3 gene in a population of patients screened for suspected cryopyrin-associated periodic syndrome (CAPS). METHODS: Since 2002, 580 patients underwent molecular analysis for NLRP3. Data on clinical presentation, response to treatment, and longterm followup were collected using a uniform questionnaire. The pattern of cytokine secretion after lipopolysaccharide stimulation from isolated monocytes was analyzed in 3 patients carrying the p.Q703K variant and 1 patient with a chronic infantile neurologic, cutaneous, articular syndrome phenotype carrying both the p.M406I and p.Q703K, and compared with 7 patients with CAPS with sure pathogenic variants and 6 healthy controls. RESULTS: The p.Q703K variant was found in 57 screened patients with an overall allelic frequency of 5%. The frequency in normal controls was 5.5%. Clinical data at the moment of molecular analysis and at followup were available in 36 patients. Two patients displayed additional mutations of NLRP3. The mean followup was 2.5 years. Thirteen patients (39%) had a final diagnosis different from the original suspicion of CAPS. The remaining 21 patients displayed a mild phenotype mainly characterized by recurrent episodes of urticarial rash and arthralgia. Only 8 patients were treated with anti-interleukin (IL)-1 treatment, with a complete response in 5 patients. The pattern of secretion of IL-1β and other cytokines (IL-6 and IL-1 receptor antagonist) in patients did not display the aberrancies observed in patients with CAPS and was similar to that observed in healthy controls. CONCLUSION: The present study confirms the weak clinical and functional effect of the p.Q703K variant.

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Consensus Conference on Clinical Management of pediatric Atopic Dermatitis. - Galli, Elena; Neri, Iria; Ricci, Giampaolo; Baldo, Ermanno; Barone, Maurizio; Belloni Fortina, Anna; Bernardini, Roberto; Berti, Irene; Caffarelli, Carlo; Calamelli, Elisabetta; Capra, Lucetta; Carello, Rossella; et al. (Ital J Pediatr, 2016)
The Italian Consensus Conference on clinical management of atopic dermatitis in children reflects the best and most recent scientific evidence, with the aim to provide specialists with a useful tool for managing this common, but complex clinical condition. Thanks to the contribution of experts in the field and members of the Italian Society of Pediatric Allergology and Immunology (SIAIP) and the Italian Society of Pediatric Dermatology (SIDerP), this Consensus statement integrates the basic principles of the most recent guidelines for the management of atopic dermatitis to facilitate a practical approach to the disease. The therapeutical approach should be adapted to the clinical severity and requires a tailored strategy to ensure good compliance by children and their parents. In this Consensus, levels and models of intervention are also enriched by the Italian experience to facilitate a practical approach to the disease.

Cross-sectional study of coeliac autoimmunity in a population of Vietnamese children. - Zanella, Sara; De Leo, Luigina; Nguyen-Ngoc-Quynh, Le; Nguyen-Duy, Bo; Not, Tarcisio; Tran-Thi-Chi, Mai; Phung-Duc, Son; Le-Thanh, Hai; Malaventura, Cristina; Vatta, Serena; Ziberna, Fabiana; Mazzocco, Martina; et al. (BMJ Open, 2016)
OBJECTIVE: The prevalence of coeliac disease (CD) in Vietnam is unknown. To fill this void, we assessed the prevalence of serological markers of CD autoimmunity in a population of children in Hanoi. SETTING: The outpatient blood drawing laboratory of the largest paediatric hospital in North Vietnam was used for the study, which was part of an international project of collaboration between Italy and Vietnam. PARTICIPANTS: Children having blood drawn for any reason were included. Exclusion criteria were age younger than 2 years, acquired or congenital immune deficiency and inadequate sample. A total of 1961 children (96%) were enrolled (838 females, 1123 males, median age 5.3 years). OUTCOMES: Primary outcome was the prevalence of positive autoimmunity to both IgA antitransglutaminase antibodies (anti-tTG) assessed with an ELISA test and antiendomysial antibodies (EMA). Secondary outcome was the prevalence of CD predisposing human leucocyte antigens (HLA) (HLA DQ2/8) in the positive children and in a random group of samples negative for IgA anti-tTG. RESULTS: The IgA anti-tTG test was positive in 21/1961 (1%; 95% CI 0.61% to 1.53%); however, EMA antibodies were negative in all. HLA DQ2/8 was present in 7/21 (33%; 95% CI 14.5% to 56.9%) of the anti-tTG-positive children and in 72/275 (26%; 95% CI 21% to 32%) of those who were negative. CONCLUSIONS: Coeliac autoimmunity is rare in Vietnam, although prevalence of HLA DQ2/8 is similar to that of other countries. We hypothesise that the scarce exposure to gluten could be responsible for these findings.

Epigenetic Signals on Plant Adaptation: A Biotic Stress Perspective. - Neto, José Ribamar Costa Ferreira; da Silva, Manassés Daniel; Pandolfi, Valesca; Crovella, Sergio; Benko-Iseppon, Ana Maria; Kido, Éderson Akio (Curr Protein Pept Sci, 2016)
For sessile organisms such as plants, regulatory mechanisms of gene expression are vital, since they remain exposed to climatic and biological threats. Thus, they have to face hazards with instantaneous reorganization of their internal environment. For this purpose, besides the use of transcription factors, the participation of chromatin as an active factor in the regulation of transcription is crucial. Chemical changes in chromatin structure affect the accessibility of the transcriptional machinery and acting in signaling, engaging/inhibiting factors that participate in the transcription processes. Mechanisms in which gene expression undergoes changes without the occurrence of DNA gene mutations in the monomers that make up DNA, are understood as epigenetic phenomena. These include (1) post-translational modifications of histones, which results in stimulation or repression of gene activity and (2) cytosine methylation in the promoter region of individual genes, both preventing access of transcriptional activators as well as signaling the recruitment of repressors. There is evidence that such modifications can pass on to subsequent generations of daughter cells and even generations of individuals. However, reports indicate that they persist only in the presence of a stressor factor (or an inductor of the above-mentioned modifications). In its absence, these modifications weaken or lose heritability, being eliminated in the next few generations. In this review, it is argued how epigenetic signals influence gene regulation, the mechanisms involved and their participation in processes of resistance to biotic stresses, controlling processes of the plant immune system.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

In vitro sensitivity to methyl-prednisolone is associated with clinical response in pediatric idiopathic nephrotic syndrome. - Cuzzoni, E; De Iudicibus, S; Stocco, G; Favretto, D; Pelin, M; Messina, G; Ghio, L; Monti, E; Pasini, A; Montini, G; Decorti, G (Clin Pharmacol Ther, 2016)
The aim of this study was to evaluate the in vitro steroid sensitivity as a predictor of clinical response to glucocorticoids in childhood idiopathic nephrotic syndrome (INS). Seventy-four patients (median age 4.33, interquartile range [IQR] 2.82-7.23; 63.5% male) were enrolled in a prospective multicenter study: in vitro steroid inhibition of patients' peripheral blood mononuclear cell proliferation was evaluated by [methyl-(3) H] thymidine incorporation assay at disease onset (T0) and after 4 weeks (T4) of treatment. Steroid dependence was associated with increased in vitro sensitivity at T4 assessed both as drug concentration inducing 50% of inhibition (IC50 ; odds ratio [OR] = 0.48, 95% confidence interval [CI] = 0.24-0.85; P = 0.0094) and maximum inhibition at the highest drug concentration (Imax ; OR = 1.13, 95% CI = 1.02-1.31; P = 0.017). IC50 > 4.4 nM and Imax < 92% at T4 were good predictors for optimal clinical response. These results suggest that this test may be useful for predicting the response to glucocorticoid therapy in pediatric INS.

Innate and adaptive immunity in self-reported nonceliac gluten sensitivity versus celiac disease. - Di Sabatino, Antonio; Giuffrida, Paolo; Fornasa, Giulia; Salvatore, Chiara; Vanoli, Alessandro; Naviglio, Samuele; De Leo, Luigina; Pasini, Alessandra; De Amici, Mara; Alvisi, Costanza; Not, Tarcisio; Rescigno, Maria; et al. (Dig Liver Dis, 2016)
BACKGROUND: Immune mechanisms have been implicated in nonceliac gluten sensitivity (NCGS), a condition characterized by intestinal and/or extraintestinal symptoms caused by the ingestion of gluten in non-celiac/non-wheat allergic individuals. AIMS: We investigated innate and adaptive immunity in self-reported NCGS versus celiac disease (CD). METHODS: In the supernatants of ex vivo-cultured duodenal biopsies from 14 self-reported NCGS patients, 9 untreated and 10 treated CD patients, and 12 controls we detected innate cytokines - interleukin (IL)-15, tumor necrosis factor-α, IL-1β, IL-6, IL-12p70, IL-23, IL-27, IL-32α, thymic stromal lymphopoietin (TSLP), IFN-α-, adaptive cytokines - interferon (IFN)-γ, IL-17A, IL-4, IL-5, IL-10, IL-13-, chemokines - IL-8, CCL1, CCL2, CCL3, CCL4, CCL5, CXCL1, CXCL10-, granulocyte colony stimulating factor (G-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF). RESULTS: Mucosal innate and adaptive cytokines, chemokines and growth factors did not differ between self-reported NCGS, treated CD and controls. On the contrary, IL-6, IL-15, IL-27, IFN-α, IFN-γ, IL-17A, IL-23, G-CSF, GM-CSF, IL-8, CCL1 and CCL4 were significantly higher in untreated CD than in self-reported NCGS, treated CD and controls, while TSLP was significantly lower in untreated CD than in self-reported NCGS, treated CD and controls. CONCLUSION: In our hands, patients with self-reported NCGS showed no abnormalities of the mucosal immune response.

Iron signature in asbestos-induced malignant pleural mesothelioma: A population-based autopsy study. - Crovella, Sergio; Bianco, Anna Monica; Vuch, Joseph; Zupin, Luisa; Moura, Ronald Rodrigues; Trevisan, Elisa; Schneider, Manuela; Brollo, Alessandro; Nicastro, Enza Maria; Cosenzi, Alessandro; Zabucchi, Giuliano; Borelli, Violetta (J Toxicol Environ Health A, 2016)
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. The development of MPM is frequently linked to inhalation of asbestos fibers. A genetic component of susceptibility to this disease is suggested by the observation that some individuals develop MPM following lower doses of asbestos exposure, whereas others exposed to higher quantities do not seem to be affected. This hypothesis is supported also by frequent reports of MPM familial clustering. Despite the widely recognized role of iron (Fe) in cellular asbestos-induced pulmonary toxicity, the role of the related gene polymorphisms in the etiology of MPM has apparently not been evaluated. Eighty-six single-nucleotide polymorphisms (SNPs) of 10 Fe-metabolism genes were examined by exploiting formalin-fixed paraffin-embedded postmortem samples from 77 patients who died due to MPM (designated AEM) and compared with 48 who were exposed to asbestos but from died in old age of cause other than asbestos (designated AENM). All subjects showed objective signs of asbestos exposure. Three SNPs, localized in the ferritin heavy polypeptide, transferrin, and hephaestin genes, whose frequencies were distributed differently in AEM and AENM populations, were identified. For ferritin and transferrin the C/C and the G/G genotypes, respectively, representing intronic polymorphisms, were significantly associated with protection against MPM and need to be considered as possible genetic markers of protection. Similarly, the C/C hephaestin SNP, a missense variation of this multicopper ferroxidase encoding gene, may be related, also functionally, with protection against MPM. In conclusion, it is proposed that three Fe metabolism-associated genes, significantly associated with protection against development of MPM, may serve as protective markers for this aggressive tumor.
Keywords: Adult; Aged; Asbestos; Autopsy; Case-Control Studies; Female; Ferritins; Gene Frequency; Genetic Markers; Humans; Iron; Lung Neoplasms; Male; Membrane Proteins; Mesothelioma; Middle Aged; Mutation, Missense; Polymorphism, Single Nucleotide; Transferrin; Young Adult

Isolated hypoplasia of abdominal wall muscles associated with fetal ascites. - Travan, Laura; Naviglio, Samuele; Cont, Gabriele; Brovedani, Pierpaolo; Davanzo, Riccardo; Demarini, Sergio (Congenit Anom (Kyoto), 2016)
We report the case of an infant born after parvovirus B19-induced fetal hydrops, who presented at birth with bilateral abdominal wall laxity, which was more evident on the flanks. Imaging exams revealed congenital hypoplasia of oblique abdominal muscles not associated with other anatomical abnormalities except for small liver calcifications. We review the medical literature and identify similar cases associated with fetal ascites. We propose that isolated hypoplasia of abdominal wall muscles can be associated with fetal ascites from various causes, and represents a separate condition from prune belly syndrome.

Lack of Evidence of Rotavirus-Dependent Molecular Mimicry as a Trigger of Celiac Disease. - Ziberna, Fabiana; De Lorenzo, Giuditta; Schiavon, Valentina; Arnoldi, Francesca; Quaglia, Sara; De Leo, Luigina; Vatta, Serena; Martelossi, Stefano; Burrone, Oscar R; Ventura, Alessandro; Not, Tarcisio (Clin Exp Immunol, 2016)
New data suggest the involvement of Rotavirus (RV) in triggering autoimmunity in celiac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured the anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy proven CD patients and 46 patients with potential-CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. By ELISA assay, we measured IgA-IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476-487 aa) which shows an homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs), containing the VP7 protein, and the double-layered RV-particles (DLPs), lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22/118 (18%) CD patients and in both paediatric (17/107, 16%) and adult (29/107, 27%) control groups, without showing a statistically significant difference among them (p=0.6, p=0.1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34/118, 29% CD patients; 66/107, 62% adult controls) and control synthetic peptides (35/118, 30% CD patients; 56/107, 52% adult controls) suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. This article is protected by copyright. All rights reserved.

Molecular diagnosis of thrombocytopenia-absent radius syndrome using next-generation sequencing. - Nicchia, E; Giordano, P; Greco, C; De Rocco, D; Savoia, A (Int J Lab Hematol, 2016)
INTRODUCTION: Thrombocytopenia-absent radius (TAR) syndrome is a rare autosomal recessive disease. Patients are compound heterozygotes for a loss-of-function allele, which in most cases is a large genomic deletion on chromosome 1q21.1 containing the RBM8A gene, and a noncoding variant located in the 5'UTR (rs139428292) or intronic (rs201779890) regions of RBM8A. As the molecular genetic testing in TAR requires multiple techniques for detection of copy-number variations (CNV) and nucleotide substitutions, we tested whether a next-generation sequencing (NGS) approach could identify both alterations. METHODS: Two unrelated families were analyzed with Ion PGM sequencing using a target panel of genes responsible for different forms of inherited thrombocytopenia. A statistical quantitative evaluation of amplicon coverage was performed to detect CNV, in particular those on the RBM8A gene. RESULTS: All the probands were apparently homozygous for the rare allele inherited by the father at the rs139428292 locus, suggesting the presence of a deletion on the maternal chromosome. The statistical analysis confirmed the hemizygous condition of RBM8A. CONCLUSION: We concluded that NGS approaches could be used as a cost-effective method for molecular investigation of TAR as they could simultaneously detect CNV and point mutations.

Mortality and its risk factors in Malawian children admitted to hospital with clinical pneumonia, 2001-12: a retrospective observational study. - Lazzerini, Marzia; Seward, Nadine; Lufesi, Norman; Banda, Rosina; Sinyeka, Sophie; Masache, Gibson; Nambiar, Bejoy; Makwenda, Charles; Costello, Anthony; McCollum, Eric D; Colbourn, Tim (Lancet Glob Health, 2016)
BACKGROUND: Few studies have reported long-term data on mortality rates for children admitted to hospital with pneumonia in Africa. We examined trends in case fatality rates for all-cause clinical pneumonia and its risk factors in Malawian children between 2001 and 2012. METHODS: Individual patient data for children (<5 years) with clinical pneumonia who were admitted to hospitals participating in Malawi's Child Lung Health Programme between 2001 and 2012 were recorded prospectively on a standardised medical form. We analysed trends in pneumonia mortality and children's clinical characteristics, and we estimated the association of risk factors with case fatality for children younger than 2 months, 2-11 months of age, and 12-59 months of age using separate multivariable mixed effects logistic regression models. FINDINGS: Between November, 2012, and May, 2013, we retrospectively collected all available hard copies of yellow forms from 40 of 41 participating hospitals. We examined 113 154 pneumonia cases, 104 932 (92·7%) of whom had mortality data and 6903 of whom died, and calculated an overall case fatality rate of 6·6% (95% CI 6·4-6·7). The case fatality rate significantly decreased between 2001 (15·2% [13·4-17·1]) and 2012 (4·5% [4·1-4·9]; ptrend<0·0001). Univariable analyses indicated that the decrease in case fatality rate was consistent across most subgroups. In multivariable analyses, the risk factors significantly associated with increased odds of mortality were female sex, young age, very severe pneumonia, clinically suspected Pneumocystis jirovecii infection, moderate or severe underweight, severe acute malnutrition, disease duration of more than 21 days, and referral from a health centre. Increasing year between 2001 and 2012 and increasing age (in months) were associated with reduced odds of mortality. Fast breathing was associated with reduced odds of mortality in children 2-11 months of age. However, case fatality rate in 2012 remained high for children with very severe pneumonia (11·8%), severe undernutrition (15·4%), severe acute malnutrition (34·8%), and symptom duration of more than 21 days (9·0%). INTERPRETATION: Pneumonia mortality and its risk factors have steadily improved in the past decade in Malawi; however, mortality remains high in specific subgroups. Improvements in hospital care may have reduced case fatality rates though a lack of sufficient data on quality of care indicators and the potential of socioeconomic and other improvements outside the hospital precludes adequate assessment of why case-fatality rates fell. Results from this study emphasise the importance of effective national systems for data collection. Further work combining this with data on trends in the incidence of pneumonia in the community are needed to estimate trends in the overall risk of mortality from pneumonia in children in Malawi. FUNDING: Bill & Melinda Gates Foundation.

Non-additive genome-wide association scan reveals a new gene associated with habitual coffee consumption. - Pirastu, Nicola; Kooyman, Maarten; Robino, Antonietta; van der Spek, Ashley; Navarini, Luciano; Amin, Najaf; Karssen, Lennart C; van Duijn, Cornelia M; Gasparini, Paolo (Sci Rep, 2016)
Coffee is one of the most consumed beverages world-wide and one of the primary sources of caffeine intake. Given its important health and economic impact, the underlying genetics of its consumption has been widely studied. Despite these efforts, much has still to be uncovered. In particular, the use of non-additive genetic models may uncover new information about the genetic variants driving coffee consumption. We have conducted a genome-wide association study in two Italian populations using additive, recessive and dominant models for analysis. This has uncovered a significant association in the PDSS2 gene under the recessive model that has been replicated in an independent cohort from the Netherlands (ERF). The identified gene has been shown to negatively regulate the expression of the caffeine metabolism genes and can thus be linked to coffee consumption. Further bioinformatics analysis of eQTL and histone marks from Roadmap data has evidenced a possible role of the identified SNPs in regulating PDSS2 gene expression through enhancers present in its intron. Our results highlight a novel gene which regulates coffee consumption by regulating the expression of the genes linked to caffeine metabolism. Further studies will be needed to clarify the biological mechanism which links PDSS2 and coffee consumption.

The one-step synthesis and surface functionalization of dumbbell-like gold-iron oxide nanoparticles: a chitosan-based nanotheranostic system. - Kostevsek, Nina; Locatelli, Erica; Garrovo, Chiara; Arena, Francesca; Monaco, Ilaria; Nikolov, Ivaylo Petrov; Sturm, Saso; Zuzek Rozman, Kristina; Lorusso, Vito; Giustetto, Pierangela; Bardini, Paola; Biffi, Stefania; et al. (Chem Commun (Camb), 2016)
The first one-step synthesis of dumbbell-like gold-iron oxide nanoparticles has been reported here. Surface functionalization with a biocompatible chitosan matrix allowed us to obtain a novel targetable diagnostic and therapeutic tool.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Resistance (R) Genes: Applications and Prospects for Plant Biotechnology and Breeding. - Pandolfi, Valesca; Neto, José Ribamar Costa Ferreira; Silva, Manassés Daniel; Amorim, Lidiane Lindinalva Barbosa; Wanderley-Nogueira, Ana Carolina; de Oliveira Silva, Roberta Lane; Kido, Éderson Akio; Crovella, Sergio; Iseppon, Ana Maria Benko (Curr Protein Pept Sci, 2016)
The discovery of novel plant resistance (R) genes (including their homologs and analogs) opened interesting possibilities for controlling plant diseases caused by several pathogens. However, due to environmental pressure and high selection operated by pathogens, several crop plants have lost specificity, broad-spectrum or durability of resistance. On the other hand, the advances in plant genome sequencing and biotechnological approaches, combined with the increasing knowledge on R-genes have provided new insights on their applications for plant genetic breeding, allowing the identification and implementation of novel and efficient strategies that enhance or optimize their use for efficiently controlling plant diseases. The present review focuses on main perspectives of application of R-genes and its co-players for the acquisition of resistance to pathogens in cultivated plants, with emphasis on biotechnological inferences, including transgenesis, cisgenesis, directed mutagenesis and gene editing, with examples of success and challenges to be faced.

Snakin: Structure, Roles and Applications of a Plant Antimicrobial Peptide. - Oliveira-Lima, Marx; Benko-Iseppon, Ana Maria; Neto, José Ribamar Costa Ferreira; Rodríguez-Decuadro, Susana; Kido, Éderson Akio; Crovella, Sergio; Pandolfi, Valesca (Curr Protein Pept Sci, 2016)
Snakins are plant antimicrobial peptides (AMPs) of the Snakin/GASA family, formed by three distinct regions: an N-terminal signal peptide; a variable site; and the GASA domain in the C-terminal region composed by twelve conserved cysteine residues that contribute to the biochemical stability of the molecule. These peptides are known to play different roles in response to a variety of biotic (i.e. induced by bacteria, fungi and nematode pathogens) and abiotic (salinity, drought and ROS) stressors, as well as in crosstalk promoted by plant hormones, with emphasis on abscisic and salicylic acid (ABA and SA, respectively). Such properties make snakin/GASA members promising biotechnological sources for potential therapeutic and agricultural applications. However, information regarding their tertiary structure, mode of action and function are not yet completely elucidated. The present review presents aspects of snakin structure, expression, functional studies and perspectives about the potential applications for agricultural and medical purposes.

ACTN1-related thrombocytopenia: identification of novel families for phenotypic characterization. - Bottega, Roberta; Marconi, Caterina; Faleschini, Michela; Baj, Gabriele; Cagioni, Claudia; Pecci, Alessandro; Pippucci, Tommaso; Ramenghi, Ugo; Pardini, Simonetta; Ngu, Loretta; Baronci, Carlo; Kunishima, Shinji; et al. (Blood, 2015)
Inherited thrombocytopenias (ITs) are a heterogeneous group of syndromic and nonsyndromic diseases caused by mutations affecting different genes. Alterations of ACTN1, the gene encoding for α-actinin 1, have recently been identified in a few families as being responsible for a mild form of IT (ACTN1-related thrombocytopenia; ACTN1-RT). To better characterize this disease, we screened ACTN1 in 128 probands and found 10 (8 novel) missense heterozygous variants in 11 families. Combining bioinformatics, segregation, and functional studies, we demonstrated that all but 1 amino acid substitution had deleterious effects. The clinical and laboratory findings of 31 affected individuals confirmed that ACTN1-RT is a mild macrothrombocytopenia with low risk for bleeding. Low reticulated platelet counts and only slightly increased serum thrombopoietin levels indicated that the latest phases of megakaryopoiesis were affected. Given its relatively high frequency in our cohort (4.2%), ACTN1-RT has to be taken into consideration in the differential diagnosis of ITs.
Keywords: Actinin; Adolescent; Adult; Aged; Aged, 80 and over; Blood Platelets; Case-Control Studies; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Platelet Count; Severity of Illness Index; Thrombocytopenia; Thrombopoiesis; Thrombopoietin

An adolescent with an altered state of mind. - Naviglio, Samuele; Papanti, Duccio; Moressa, Valentina; Ventura, Alessandro (BMJ, 2015)
Keywords: Adolescent; Cannabinoids; Designer Drugs; Hallucinations; Humans; Male; Substance-Related Disorders

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

A brain and heart connection: X-linked periventricular heterotopia. - Naviglio, Samuele; Bruno, Irene; Zanus, Caterina; Faletra, Flavio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Adolescent; Brain; Diagnosis, Differential; DNA Mutational Analysis; Epilepsy; Female; Filamins; Humans; Magnetic Resonance Imaging; Mutation; Periventricular Nodular Heterotopia

Characterization of 14 novel deletions underlying Rubinstein-Taybi syndrome: an update of the CREBBP deletion repertoire. - Rusconi, Daniela; Negri, Gloria; Colapietro, Patrizia; Picinelli, Chiara; Milani, Donatella; Spena, Silvia; Magnani, Cinzia; Silengo, Margherita Cirillo; Sorasio, Lorena; Curtisova, Vaclava; Cavaliere, Maria Luigia; Prontera, Paolo; et al. (Hum Genet, 2015)
Rubinstein-Taybi syndrome (RSTS) is a rare, clinically heterogeneous disorder characterized by cognitive impairment and several multiple congenital anomalies. The syndrome is caused by almost private point mutations in the CREBBP (~55% of cases) and EP300 (~8%) genes. The CREBBP mutational spectrum is variegated and characterized by point mutations (30-50 %) and deletions (~10%). The latter are diverse in size and genomic position and remove either the whole CREBBP gene and its flanking regions or only an intragenic portion. Here, we report 14 novel CREBBP deletions ranging from single exons to the whole gene and flanking regions which were identified by applying complementary cytomolecular techniques: fluorescence in situ hybridization, multiplex ligation-dependent probe amplification and array comparative genome hybridization, to a large cohort of RSTS patients. Deletions involving CREBBP account for 23% of our detected CREBBP mutations, making an important contribution to the mutational spectrum. Genotype-phenotype correlations revealed that patients with CREBBP deletions extending beyond this gene did not always have a more severe phenotype than patients harboring CREBBP point mutations, suggesting that neighboring genes play only a limited role in the etiopathogenesis of CREBBP-centerd contiguous gene syndrome. Accordingly, the extent of the deletion is not predictive of the severity of the clinical phenotype.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Cohort Studies; CREB-Binding Protein; Female; Humans; Infant; Infant, Newborn; Male; Middle Aged; Point Mutation; Rubinstein-Taybi Syndrome; Sequence Deletion

Clinical aspects of Fanconi anemia individuals with the same mutation of FANCF identified by next generation sequencing. - Nicchia, Elena; Benedicenti, Francesco; Rocco, Daniela De; Greco, Chiara; Bottega, Roberta; Inzana, Francesca; Faleschini, Michela; Bonin, Serena; Cappelli, Enrico; Mogni, Massimo; Stanzial, Franco; Svahn, Johanna; et al. (Birth Defects Res A Clin Mol Teratol, 2015)
BACKGROUND: Fanconi anemia (FA) is a rare genetic disease characterized by congenital malformations, aplastic anemia and increased risk of developing malignancies. FA is genetically heterogeneous as it is caused by at least 17 different genes. Among these, FANCA, FANCC, and FANCG account for approximately 85% of the patients whereas the remaining genes are mutated in only a small percentage of cases. For this reason, the molecular diagnostic process is complex and not always extended to all the FA genes, preventing the characterization of individuals belonging to rare groups. METHODS: The FA genes were analyzed using a next generation sequencing approach in two unrelated families. RESULTS: The analysis identified the same, c.484_485del, homozygous mutation of FANCF in both families. A careful examination of three electively aborted fetuses in one family and one affected girl in the other indicated an association of the FANCF loss-of-function mutation with a severe phenotype characterized by multiple malformations. CONCLUSION: The systematic use of next generation sequencing will allow the recognition of individuals from rare complementation groups, a better definition of their clinical phenotypes, and consequently, an appropriate genetic counseling. Birth Defects Research (Part A) 103:1003-1010, 2015. © 2015 Wiley Periodicals, Inc.

Coeliac disease in the ERA of the new ESPGHAN and BSPGHAN guidelines: a prospective cohort study. - Benelli, Elisa; Carrato, Valentina; Martelossi, Stefano; Ronfani, Luca; Not, Tarcisio; Ventura, Alessandro (Arch Dis Child, 2015)
OBJECTIVE: To evaluate the consequences of the last European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN) guidelines for the diagnosis of coeliac disease (CD) by means of a prospective study. DESIGN: Prospective cohort study. SETTING: Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy). PATIENTS: Children diagnosed with CD without a duodenal biopsy (group 1), following the last ESPGHAN and BSPGHAN guidelines, and children diagnosed with a duodenal biopsy, matched for sex, age and year of diagnosis (group 2), were prospectively enrolled over a 3-year period. All patients were put on a gluten-free diet (GFD) and were followed up for clinical conditions and laboratory testing at 6 months every year since diagnosis (median follow up: 1.9 years). OUTCOME MEASURES: Resolution of symptoms, body mass index, laboratory testing (haemoglobin, anti-transglutaminase IgA), adherence to a GFD, quality of life, and supplementary post-diagnosis medical consultations. RESULTS: 51 out of 468 (11%) patients were diagnosed without a duodenal biopsy (group 1; median age 2.1 years) and matched to 92 patients diagnosed with a biopsy (group 2; median age 2.4 years). At the end of follow-up the two groups were statistically comparable in terms of clinical and nutritional status, anti-transglutaminase IgA antibody titres, quality of life, adherence to a GFD, and number of supplementary medical consultations. CONCLUSIONS: On the basis of this prospective study, diagnosis of CD can be reliably performed without a duodenal biopsy in approximately 11% of cases. At least during a medium-term follow-up, this approach has no negative consequences relating to clinical remission, adherence to diet, and quality of life of children with CD.

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Dysplastic bone marrow changes during maintenance therapy for acute leukemia. - Chinello, Matteo; Naviglio, Samuele; Shardlow, Alison; Severino, Alessandro; Ventura, Alessandro; Locasciulli, Anna (J Pediatr Hematol Oncol, 2015)
We describe the case of an 8-year-old girl with common precursor B-cell acute lymphoblastic leukemia who presented with severe pancytopenia during maintenance therapy with methotrexate and 6-mercaptopurine. The bone marrow smear showed moderate hypocellularity and trilinear dysplastic changes consistent with a diagnosis of drug toxicity, with no evidence of lymphoblasts. Flow cytometric immunophenotyping was negative for leukemic cells. Blood cell counts normalized after treatment with folinic acid. Maintenance therapy was gradually restarted and she remained well at follow-up visits. Myelotoxicity from methotrexate and 6-mercaptopurine may represent an unpredictable incident during an otherwise uneventful maintenance therapy, and may occur independently of other organ toxicities.
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Bone Marrow Diseases; Child; Disease Management; Female; Follow-Up Studies; Humans; Methotrexate; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Prognosis

Efficacy of intravenous immunoglobulin therapy in giant cell hepatitis with autoimmune hemolytic anemia: A multicenter study. - Marsalli, Giulia; Nastasio, Silvia; Sciveres, Marco; Calvo, Pier Luigi; Ramenghi, Ugo; Gatti, Simona; Albano, Veronica; Lega, Sara; Ventura, Alessandro; Maggiore, Giuseppe (Clin Res Hepatol Gastroenterol, 2015)
BACKGROUND AND OBJECTIVE: Giant cell hepatitis with autoimmune hemolytic anemia (GCH-AHA) is a rare disease of infancy, of possible autoimmune mechanism with poor prognosis due to its scarce response to immunosuppressive drugs. The aim of this retrospective multicenter study was to evaluate the efficacy and safety of intravenous immunoglobulin (IVIg) treatment in inducing and maintaining remission of the liver disease, in patients with GCH-AHA. METHODS: Seven children with GCH-AHA, four newly diagnosed, and three in relapse, being treated with different therapies, received one to three IVIg infusions (0.5 to 2g/kg) in association with other immunosuppressive drugs. Subsequently five of them received monthly sequential IVIg infusions (mean 13.4, range 7-24). RESULTS: IVIg infusions as first-line therapy associated with prednisone and other immunosuppressive drugs significantly (P=0.04) reduced the aminotransferase activity in all patients and normalized prothombin activity in the only patient with severe liver dysfunction. Sequential monthly IVIg infusions determined a steroid-sparing effect and allowed a complete or partial remission in all patients, although with temporary efficacy, since relapse of the hemolytic anemia and/or of liver disease occurred in all patients. IVIg infusions were associated with mild side effects in two patients. CONCLUSIONS: IVIg infusion can be safely and effectively administered in patients with severe GCH-AHA at diagnosis, or in case of relapse, in association with other immunosuppressive drugs. Repeated IVIg infusions may help maintain remission, however, due to their temporary efficacy, they should not be routinely employed.

Fainting Starting Parenteral Nutrition. - Pederiva, Federica; Barbi, Egidio; Zennaro, Floriana; Neri, Elena (Pediatr Emerg Care, 2015)
Complications such as mechanical accidents, infections, and thrombosis are commonly described in the presence of a central venous catheter. We present a case of a boy who had fainting episodes due to dislocation of a central venous catheter.

Food protein-induced enterocolitis syndrome caused by fish and/or shellfish in Italy. - Miceli Sopo, Stefano; Monaco, Serena; Badina, Laura; Barni, Simona; Longo, Giorgio; Novembre, Elio; Viola, Serena; Monti, Giovanna (Pediatr Allergy Immunol, 2015)
BACKGROUND: The study describes the demographic features, culprit foods, clinical features and outcomes for children presenting with acute fish and/or shellfish food protein-induced enterocolitis syndrome (FPIES) in four Italian paediatric allergy centres. METHODS: A retrospective/prospective study was undertaken. All children diagnosed with fish or shellfish FPIES were enrolled. The diagnosis of FPIES was based on Sicherer's or Miceli Sopo clinical criteria. Skin prick tests (SPT) were performed in all patients, at the time of diagnosis and prior to OFC. RESULTS: Seventy children were enrolled. Mean age at first episode was 14 months (range 6-46 months); mean age at diagnosis was 34 months (range 6-164 months). Sole and cod were the fish most commonly implicated. Fifty-seven of 70 (81%) children had FPIES exclusively to fish, 37 of 57 (65%) children had single-fish FPIES, 20 of 57 (35%) multiple-fish FPIES, nine of 70 (13%) presented adverse reactions exclusively to shellfish, and four of 70 (6%) presented adverse reactions to both fish and shellfish. Only four (5.7%) children presented episodes of acute FPIES with different foods (2 to cow's milk, 1 to egg, 1 to beef); in all cases, onset was prior to that of fish or shellfish FPIES. Fifteen of 70 (21%) children tolerated fish other than the offending fish. Twenty-four of 70 (34%) children achieved tolerance (age range 24-102 months). CONCLUSIONS: The chief peculiarities of acute fish and shellfish FPIES, compared to more frequent cow's milk or soy FPIES, are (i) later age of onset, (ii) longer persistence and (iii) possibility of tolerating fish other than the offending fish. Adverse reactions with shellfish are possible.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

The novel dual PI3K/mTOR inhibitor NVP-BGT226 displays cytotoxic activity in both normoxic and hypoxic hepatocarcinoma cells. - Simioni, Carolina; Cani, Alice; Martelli, Alberto M; Zauli, Giorgio; Alameen, Ayman A M; Ultimo, Simona; Tabellini, Giovanna; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
Hepatocellular carcinoma (HCC) is one of the most common lethal human malignancies worldwide and its advanced status is frequently resistant to conventional chemotherapeutic agents and radiation. We evaluated the cytotoxic effect of the orally bioavailable dual PI3K/mTOR inhibitor, NVP-BGT226, on a panel of HCC cell lines, since hyperactivated PI3K/Akt/mTOR signaling pathway could represent a biomolecular target for Small Inhibitor Molecules in this neoplasia. We analyzed the drug activity in both normoxia and hypoxia conditions, the latter playing often a relevant role in the induction of chemoresistance and angiogenesis.In normoxia NVP-BGT226 caused cell cycle arrest in the G0/G1 phase of the cell cycle, induced apoptosis and autophagy at low concentrations. Interestingly the drug inactivated p-Akt and p-S6 at < 10 nM concentration.In hypoxia NVP-BGT226 maintained its cytotoxic efficacy at the same concentration as documented by MTT assays and Western blot analysis. Moreover, the drug showed in hypoxia inhibitory properties against angiogenesis by lowering the expression of the transcription factor HIF-1α and of VEGF.Our results indicate that NVP-BGT226 has a potent cytotoxic effect on HCC cell lines also in hypoxia condition, thus emerging as a potential candidate for cancer treatment in HCC targeted therapy.

A pneumonia that does not improve. - Naviglio, Samuele; Chinello, Matteo; Ventura, Alessandro (Arch Dis Child Educ Pract Ed, 2015)
Keywords: Airway Obstruction; Bronchoscopy; Child, Preschool; Foreign Bodies; Humans; Pneumonia; Radiography, Thoracic

Polymorphisms in sweet taste genes (TAS1R2 and GLUT2), sweet liking, and dental caries prevalence in an adult Italian population. - Robino, Antonietta; Bevilacqua, Lorenzo; Pirastu, Nicola; Situlin, Roberta; Di Lenarda, Roberto; Gasparini, Paolo; Navarra, Chiara Ottavia (Genes Nutr, 2015)
The aim of the study was to assess the relationship between sweet taste genes and dental caries prevalence in a large sample of adults. In addition, the association between sweet liking and sugar intake with dental caries was investigated. Caries was measured by the decayed, missing, filled teeth (DMFT) index in 647 Caucasian subjects (285 males and 362 females, aged 18-65 years), coming from six villages in northeastern Italy. Sweet liking was assessed using a 9-point scale, and the mean of the liking given by each individual to specific sweet food and beverages was used to create a sweet liking score. Simple sugar consumption was estimated by a dietary history interview, considering both added sugars and sugar present naturally in foods. Our study confirmed that polymorphisms in TAS1R2 and GLUT2 genes are related to DMFT index. In particular, GG homozygous individuals for rs3935570 in TAS1R2 gene (p value = 0.0117) and GG homozygous individuals for rs1499821 in GLUT2 gene (p value = 0.0273) showed higher DMFT levels compared to both heterozygous and homozygous for the alternative allele. Furthermore, while the relationship sugar intake-DMFT did not achieve statistical significance (p value = 0.075), a significant association was identified between sweet liking and DMFT (p value = 0.004), independent of other variables. Our study showed that sweet taste genetic factors contribute to caries prevalence and highlighted the role of sweet liking as a predictor of caries risk. Therefore, these results may open new perspectives for individual risk identification and implementation of target preventive strategies, such as identifying high-risk patients before caries development.

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

A Sensitive Electrochemiluminescence Immunosensor for Celiac Disease Diagnosis Based on Nanoelectrode Ensembles. - Habtamu, Henok B; Sentic, Milica; Silvestrini, Morena; De Leo, Luigina; Not, Tarcisio; Arbault, Stephane; Manojlovic, Dragan; Sojic, Neso; Ugo, Paolo (Anal Chem, 2015)

Serum anti-tissue transglutaminase antibodies detected during febrile illness may not be produced by the intestinal mucosa. - De Leo, Luigina; Quaglia, Sara; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Maschio, Massimo; Not, Tarcisio (J Pediatr, 2015)
Anti-transglutaminase antibodies are the diagnostic marker of celiac disease, and are considered to be synthesized only by intestinal B-lymphocytes. During an infectious disease, these antibodies are transiently detected in serum. We show that these infection-triggered antibodies may not originate in the intestinal mucosa and are not an indication of celiac disease.
Keywords: Autoantibodies; Celiac Disease; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; GTP-Binding Proteins; Humans; Intestinal Mucosa; Male; Transglutaminases

Splenic Infarction in Acute Infectious Mononucleosis. - Naviglio, Samuele; Abate, Maria Valentina; Chinello, Matteo; Ventura, Alessandro (J Emerg Med, 2015)
BACKGROUND: The evaluation of a febrile patient with acute abdominal pain represents a frequent yet possibly challenging situation in the emergency department (ED). Splenic infarction is an uncommon complication of infectious mononucleosis, and may have a wide range of clinical presentations, from dramatic to more subtle. Its pathogenesis is still incompletely understood, yet it may be associated with the occurrence of transient prothrombotic factors. CASE REPORT: We report the case of a 14-year-old boy who presented with fever, sore throat, left upper quadrant abdominal pain, and splenomegaly, with no history of recent trauma. Laboratory tests revealed a markedly prolonged activated partial thromboplastin time and positive lupus anticoagulant. Abdominal ultrasonography showed several hypoechoic areas in the spleen consistent with multiple infarctions. Magnetic resonance imaging eventually confirmed the diagnosis. He was admitted for observation and supportive treatment, and was discharged in good condition after 7 days. WHY SHOULD AN EMERGENCY PHYSICIAN BE AWARE OF THIS?: Spontaneous splenic infarction should be considered in the differential list of patients presenting with left upper quadrant abdominal pain and features of infectious mononucleosis; the diagnosis, however, may not be straightforward, as clinical presentation may also be subtle, and abdominal ultrasonography, which is often used as a first-line imaging modality in pediatric EDs, has low sensitivity in this scenario and may easily miss it. Furthermore, although treatment is mainly supportive, close observation for possible complications is necessary.

Subcutaneous panniculitis-like T-cell lymphoma presenting with diffuse cutaneous edema in a 2-year-old child. - Chinello, Matteo; Naviglio, Samuele; Remotti, Daniele; Locasciulli, Anna; Ventura, Alessandro (J Pediatr Hematol Oncol, 2015)
Keywords: Child, Preschool; Edema; Humans; Lymphoma, T-Cell; Male; Panniculitis; Skin Diseases

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

Triple Akt inhibition as a new therapeutic strategy in T-cell acute lymphoblastic leukemia. - Cani, Alice; Simioni, Carolina; Martelli, Alberto M; Zauli, Giorgio; Tabellini, Giovanna; Ultimo, Simona; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive neoplastic disorder in which chemotherapy resistance and refractory relapses occur, with a poorer prognostic outcome.Constitutively active PI3K/Akt/mTOR pathway is a common feature of T-ALL upregulating cell proliferation, survival and drug resistance. This pathway is currently under clinical trials with small molecules inhibitors (SMI).To verify whether a multi-inhibition treatment against Akt protein could enhance the efficacy of individual drug administration and overcome drug resistance as well as to obtain a decrease in single drug concentration, we tested on T-ALL cell lines the effects of combined treatments with three Akt inhibitors with different mode of action, GSK690693, MK-2206 and Perifosine.In cells with hyperactivated Akt, combined administration of the drugs displayed a significant synergistic and cytotoxic effect and affected PI3K/Akt/mTOR pathway at much lower concentration than single drug use. Highest synergistic effect for full inhibition of Akt was also related to the timing of every drug administration. Furthermore the triple treatment had greater efficacy in inducing cell cycle arrest in G0/G1 phase and both apoptosis and autophagy.Targeting Akt as a key protein of PI3K/Akt/mTOR pathway with multiple drugs might represent a new and promising pharmacological strategy for treatment of T-ALL patients.

Validation of the Italian translation of the affective neuroscience personality scales. - Pascazio, Lorenzo; Bembich, Stefano; Nardone, Ilaria B; Vecchiet, Cristina; Guarino, Giuseppina; Clarici, Andrea (Psychol Rep, 2015)
The theoretical perspective on affective neuroscience advanced by Panksepp, identified six basic innate affective systems: the SEEK, FEAR, ANGER, SADNESS, PLAY, and CARE systems. (3) It has been proposed that the fundamental elements of human personality and its variants may be based on the different expressions of these basic emotional systems and their combinations. A self-report inventory, the Affective Neuroscience Personality Scales (ANPS), has been devised with the aim of studying and evaluating personality from this perspective. This study reports data on the initial validation of ANPS Italian translation on a sample of 418 adult participants. Descriptive statistics for each scale were calculated, assessing also their internal consistency, as a measure of reliability and factorial validity. Acceptable internal consistency was found in all but one scale (SADNESS), and a second-order factor analysis identified a more general affective feature of personality hinging on relational characteristics, independent of the dimensions of general positive and negative affect.
Keywords: Adolescent; Adult; Affect; Aged; Aged, 80 and over; Female; Humans; Italy; Male; Middle Aged; Neurosciences; Personality; Personality Inventory; Psychometrics; Young Adult

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

A boy with sudden headache. - Norbedo, Stefania; Naviglio, Samuele; Murru, Flora Maria; Cavallin, Roberta; Giurici, Nagua; Rabusin, Marco; Barbi, Egidio (Pediatr Emerg Care, 2014)
Headache is a common presenting complaint in pediatric emergency departments. The goal of emergent evaluation is to identify those children with potentially life-threatening conditions. We present the case of an adolescent boy presenting with headache and hypertension who was diagnosed with a catecholamine-secreting abdominal paraganglioma. Genetic testing eventually led to the diagnosis of SDHB-related hereditary paraganglioma-pheochromocytoma syndrome. Alarm features ("red flags") in children presenting with headache are reviewed, as well as the main features of paragangliomas and the indications for genetic testing.
Keywords: Abdominal Neoplasms; Adolescent; Emergencies; Headache; Humans; Male; Paraganglioma

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Development of an enzyme-linked immunosorbent assay for Bartonella henselae infection detection. - Ferrara, F; Di Niro, R; D'Angelo, S; Busetti, M; Marzari, R; Not, T; Sblattero, D (Lett Appl Microbiol, 2014)
UNLABELLED: Several serological diagnostics rely on enzyme-linked immunosorbent assay (ELISA) to detect bacterial infections. However, for some pathogens, including Bartonella henselae, diagnosis still depends on manually intensive, time-consuming assays including micro-immunofluorescence, Western blotting or indirect immunofluorescence. For such pathogens, there is obviously still a need to identify antigens to establish a reliable, fast and high-throughput assay (Dupon et al. ). We evaluated two B. henselae proteins to develop a novel serological ELISA: a well-known antigen, the 17-kDa protein, and GroEL, identified during this study by a proteomic approach. When serum IgG were tested, the specificity and sensitivity were 76 and 65·7% for 17-kDa, respectively, and 82 and 42·9% for GroEL, respectively. IgM were found to be more sensitive and specific for both proteins: 17-kDa protein, specificity 86·2% and sensitivity 75%; GroEL, specificity 97·7% and sensitivity 45·3%. IgM antibodies were also measured in lymphoma patients and patients with Mycobacterium tuberculosis infection to assess the usefulness of our ELISA to distinguish them from B. henselae infected patients. The resulting specificities were 89·1 and 93·5% for 17-kDa protein and GroEL, respectively. Combining the results from the two tests, we obtained a sensitivity of 82·8% and a specificity of 83·9%. Our work described and validated a proteomic approach suitable to identify immunogenic proteins useful for developing a serological test of B. henselae infection. SIGNIFICANCE AND IMPACT OF THE STUDY: A reliable serological assay for the diagnosis of Cat Scratch Disease (CSD) - a pathological condition caused by Bartonella henselae infection - has not yet been developed. Such an assay would be extremely useful to discriminate between CSD and other pathologies with similar symptoms but different aetiologies, for example lymphoma or tuberculosis. We investigate the use of two B. henselae proteins - GroEL and 17-kDa - to develop a serological-based ELISA, showing promising results with the potential for further development as an effective tool for the differential diagnosing of B. henselae infection.
Keywords: Adolescent; Adult; Amino Acid Sequence; Antibodies, Bacterial; Antigens, Bacterial; Bacterial Proteins; Bartonella henselae; Case-Control Studies; Cat-Scratch Disease; Chaperonin 60; Child; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin M; Lymphoma; Male; Molecular Sequence Data; ROC Curve; Tuberculosis, Pulmonary; Young Adult

Diagnostic accuracy of ultrasonography for hand bony fractures in paediatric patients. - Neri, Elena; Barbi, Egidio; Rabach, Ingrid; Zanchi, Chiara; Norbedo, Stefania; Ronfani, Luca; Guastalla, Veronica; Ventura, Alessandro; Guastalla, Pierpaolo (Arch Dis Child, 2014)
OBJECTIVE: Hand fractures are common in childhood, and radiography is the standard diagnostic procedure. US has been used to evaluate bone injuries, mainly in adults for long-bone trauma; there are only a few studies about hand fractures in children. The purpose of this study was to evaluate and confirm the safety and applicability of the US diagnostic procedure in comparison to X-ray diagnosis. STUDY DESIGN: This cross-sectional study involved a convenience sample of young patients (between 2 and 17 years old) who were taken to the emergency department due to hand trauma. After clinical assessment, patients with a suspected hand fracture first underwent X-ray, and subsequently US examination by two different operators; a radiologist experienced in US and a trained emergency physician in "double-blind" fashion. US and radiographic findings were then compared, and sensitivity as well as specificity was calculated. RESULTS: A total of 204 patients were enrolled in the study. Seventy-nine fractures of phalanges or metacarpals were detected by standard radiography. When US imaging was performed by an expert radiologist, 72 fractures were detected with sensitivity and a specificity of 91.1% and 97.6%, respectively. Sensitivity and specificity were found to be (respectively) 91.5% and 96.8% when US was performed by the ED physicians. CONCLUSIONS: US imaging showed excellent sensitivity and specificity results in the diagnosis of hand fractures in children. The study also showed a great agreement between the results of the US carried out by the senior radiologist and those carried out by the paediatric emergency physician, suggesting that US can be performed by an ED physician, allowing a rapid and accurate evaluation in ED and could become the first diagnostic approach whenever a hand fracture is suspected.
Keywords: Adolescent; Child; Child, Preschool; Cross-Sectional Studies; Double-Blind Method; Emergency Service, Hospital; Female; Fractures, Bone; Hand Bones; Humans; Italy; Male; Sensitivity and Specificity

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

HLA-B35, a common genetic trait, in a familial case of Henoch-Schoenlein purpura and Berger's disease. - Pellegrin, M C; Matarazzo, L; Neri, E; Pennesi, M; Crovella, S (Genet Mol Res, 2014)
Nephritis characterized by IgA mesangial depositions has been described both in Henoch-Schoenlein purpura (HSP) and in Berger's disease (BD), but common genetic traits are still uncertain. We report here the case of two brothers, the first affected by HSP with persistent nephritis and the second by BD, accidentally discovered as silent microhematuria 1 year after HSP onset in the first brother. HLA genotyping demonstrated the presence of HLA-B35 in both patients. Our findings reinforce the need to screen for urinary abnormalities in family members of patients affected by HSP nephritis to identify a silent IgA nephropathy.
Keywords: Adolescent; Child; Female; Genotype; Glomerulonephritis, IGA; HLA-B35 Antigen; Humans; Male; Middle Aged; Nephritis; Phenotype; Purpura, Schoenlein-Henoch

Increased levels of C-C chemokine RANTES in asbestos exposed workers and in malignant mesothelioma patients from an hyperendemic area. - Comar, Manola; Zanotta, Nunzia; Bonotti, Alessandra; Tognon, Mauro; Negro, Corrado; Cristaudo, Alfonso; Bovenzi, Massimo (PLoS One, 2014)
BACKGROUND: Asbestos-induced mesothelial inflammatory processes are thought to be the basic mechanisms underlying Malignant Mesothelioma (MM) development. Detection of MM often occurs at late stage due to the long and unpredictable latent period and the low incidence in asbestos exposed individuals. The aim of this study was to investigate early immunological biomarkers to characterize the prognostic profile of a possible asbestos-induced disease, in subjects from a MM hyperendemic area. METHODS: The Luminex Multiplex Panel Technology was used for the simultaneous measurement of serum levels of a large panel of 47 analytes, including cytokines and growth factors, from workers previously exposed to asbestos (Asb-workers), asbestos-induced MM patients and healthy subjects. In addition, to explore the influence on serum cytokines profile exerted by SV40 infection, a cofactor in MM development, a quantitative real time PCR was performed for sequences detection in the N-terminal and intronic regions of the SV40 Tag gene. Statistical analysis was done by means of the Mann-Whitney test and the Kruskall-Wallis test for variance analysis. RESULTS: A variety of 25 cytokines linked to pulmonary inflammation and tumor development were found significantly associated with Asb-workers and MM patients compared with healthy controls. A specific pattern of cytokines were found highly expressed in Asb-workers: IFN-alpha (p<0.05), EOTAXIN (p<0.01), RANTES (p<0.001), and in MM patients: IL-12(p40), IL-3, IL-1 alpha, MCP-3, beta-NGF, TNF-beta, RANTES (p<0.001). Notably, the chemokine RANTES measured the highest serum level showing an increased gradient of concentration from healthy subjects to Asb-workers and MM patients (p<0.001), independently of SV40 infection. CONCLUSION: This study shows that, in subjects from an hyperendemic area for MM, the C-C chemokine RANTES is associated with the exposure to asbestos fibres. If validated in larger samples, this factor could have the potential to be a critical biomarker for MM prognosis as recently reported for breast tumor.
Keywords: Aged; Aged, 80 and over; Asbestos; Biomarkers, Tumor; Case-Control Studies; Chemokine CCL5; Cytokines; Endemic Diseases; Gene Expression; Gene Expression Profiling; Humans; Lung Neoplasms; Mesothelioma; Middle Aged; Occupational Exposure; Simian virus 40; Viral Proteins

Influence of urine volume on the assessment of intestinal permeability in affected children by multiple sugar probes. - Addobbati, Riccardo; Pascolo, Lorella; Di Toro, Nicola; Sebastiani, Giulia B; Martellossi, Stefano; Not, Tarcisio (Clin Chem Lab Med, 2014)
BACKGROUND: In this study we have looked at the reliability of a multi-sugar test in a pediatric patient population and its accuracy at small urine volumes to evaluate intestinal permeability. METHODS: Out of 117 subjects enrolled, 31 were healthy and 86 were sick. A solution containing lactulose, rhamnose, sucrose, and sucralose was administered to subjects who were on fasting; the urine excreted during 5 h was collected and measured. Samples were analyzed by gas chromatography-tandem mass spectrometry and results were expressed as percentage of sugar recoveries and lactulose/rhamnose (L/R) ratio. RESULTS: The analyses showed a clear effect of low urinary volumes (≤240 mL) particularly affecting rhamnose excretion in healthy subjects and sucrose and sucralose recovery in diseased children. Despite the low rhamnose recovery, as lactulose is not similarly affected, the diagnostic reliability of L/R ratio is well preserved at low diuresis conditions. However, this ratio can be useful to discriminate acute conditions vs. clinical remissions only at high urine volumes. Data also suggest potential diagnostic applicability of sucrose and sucralose in children at high urine volumes. CONCLUSIONS: In conclusion, the multi-sugar test has a good predictivity in pediatric subjects but results must be carefully interpreted in the face of reduced diuresis.
Keywords: Carbohydrates; Child, Preschool; Diuresis; Female; Gas Chromatography-Mass Spectrometry; Gastrointestinal Diseases; Humans; Infant; Intestines; Lactulose; Male; Permeability; Rhamnose; Sucrose

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Levels of circulating TNF-related apoptosis-inducing ligand in celiac disease. - Celeghini, Claudio; Not, Tarcisio; Norcio, Alessia; Monasta, Lorenzo; Secchiero, Paola (Exp Ther Med, 2014)
It has previously been demonstrated that the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL) are significantly lower in patients with type 1 diabetes (T1D) than in normal age- and gender-matched controls. Since celiac disease (CD) is often associated with T1D, a retrospective study was performed to analyze the sera of a cohort of pediatric subjects: i) patients with CD at onset (n=100); ii) patients with potential CD (n=45); iii) patients with CD associated with other auto-immune diseases (n=17); and iv) patients with eosinophilic esophagitis (n=15). Among the patients with CD, 49 were also analyzed after six months on a gluten-free diet, while data were also available for 13 patients after one year on a gluten-free diet. No significant differences were found in the circulating levels of TRAIL between the patients with CD and the patients with either eosinophilic esophagitis or potential CD. Patients with CD associated with other auto-immune diseases showed significantly lower levels of TRAIL when compared with patients with CD alone. The gluten-free diet did not significantly modify the levels of circulating TRAIL at 6 or 12 months. Thus, although T1D and CD share common immunological features, the circulating levels of TRAIL show a significant difference between the two pathologies, and do not appear to be modulated in CD.

Long-term follow-up in children with benign convulsions associated with gastroenteritis. - Verrotti, Alberto; Moavero, Romina; Vigevano, Federico; Cantonetti, Laura; Guerra, Azzurra; Spezia, Elisabetta; Tricarico, Antonella; Nanni, Giuliana; Agostinelli, Sergio; Chiarelli, Francesco; Parisi, Pasquale; Capovilla, Giuseppe; et al. (Eur J Paediatr Neurol, 2014)
BACKGROUND: The outcome of benign convulsions associated with gastroenteritis (CwG) has generally been reported as being excellent. However, these data need to be confirmed in studies with longer follow-up evaluations. AIM: To assess the long-term neurological outcome of a large sample of children presenting with CwG. METHODS: We reviewed clinical features of 81 subjects presenting with CwG (1994-2010) from three different Italian centers with a follow-up period of at least 3 years. RESULTS: Follow-up period ranged from 39 months to 15 years (mean 9.8 years). Neurological examination and cognitive level at the last evaluation were normal in all the patients. A mild attention deficit was detected in three cases (3.7%). Fourteen children (17.3%) received chronic anti-epileptic therapy. Interictal EEG abnormalities detected at onset in 20 patients (24.7%) reverted to normal. Transient EEG epileptiform abnormalities were detected in other three cases (3.7%), and a transient photosensitivity in one (1.2%). No recurrence of CwG was observed. Three patients (3.7%) presented with a febrile seizure and two (2.5%) with an unprovoked seizure, but none developed epilepsy. CONCLUSIONS: The long-term evaluation of children with CwG confirms the excellent prognosis of this condition, with normal psychomotor development and low risk of relapse and of subsequent epilepsy.
Keywords: Adolescent; Anticonvulsants; Attention Deficit Disorder with Hyperactivity; Child; Child, Preschool; Electroencephalography; Epilepsy; Female; Gastroenteritis; Humans; Longitudinal Studies; Male; Neurologic Examination; Retrospective Studies

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Mutations of cytochrome c identified in patients with thrombocytopenia THC4 affect both apoptosis and cellular bioenergetics. - De Rocco, Daniela; Cerqua, Cristina; Goffrini, Paola; Russo, Giovanna; Pastore, Annalisa; Meloni, Francesca; Nicchia, Elena; Moraes, Carlos T; Pecci, Alessandro; Salviati, Leonardo; Savoia, Anna (Biochim Biophys Acta, 2014)
Inherited thrombocytopenias are heterogeneous diseases caused by at least 20 genes playing different role in the processes of megakaryopoiesis and platelet production. Some forms, such as thrombocytopenia 4 (THC4), are very rare and not well characterized. THC4 is an autosomal dominant mild thrombocytopenia described in only one large family from New Zealand and due to a mutation (G41S) of the somatic isoform of the cytochrome c (CYCS) gene. We report a novel CYCS mutation (Y48H) in patients from an Italian family. Similar to individuals carrying G41S, they have platelets of normal size and morphology, which are only partially reduced in number, but no prolonged bleeding episodes. In order to determine the pathogenetic consequences of Y48H, we studied the effects of the two CYCS mutations in yeast and mouse cellular models. In both cases, we found reduction of respiratory level and increased apoptotic rate, supporting the pathogenetic role of CYCS in thrombocytopenia.
Keywords: Amino Acid Sequence; Animals; Apoptosis; Base Sequence; Cells, Cultured; Child, Preschool; Cytochromes c; DNA Mutational Analysis; Embryo, Mammalian; Energy Metabolism; Family Health; Female; Fibroblasts; Humans; Lung; Male; Mice; Molecular Sequence Data; Mutation, Missense; Oxygen Consumption; Pedigree; Saccharomyces cerevisiae; Sequence Homology, Amino Acid; Thrombocytopenia

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

Polyubiquitinated proteins, proteasome, and glycogen characterize the particle-rich cytoplasmic structure (PaCS) of neoplastic and fetal cells. - Necchi, Vittorio; Sommi, Patrizia; Vitali, Agostina; Vanoli, Alessandro; Savoia, Anna; Ricci, Vittorio; Solcia, Enrico (Histochem Cell Biol, 2014)
A particle-rich cytoplasmic structure (PaCS) concentrating ubiquitin-proteasome system (UPS) components and barrel-like particles in clear, cytoskeleton- and organelle-free areas has recently been described in some neoplasms and in genetic or infectious diseases at risk of neoplasia. Ultrastructurally similar particulate cytoplasmic structures, interpreted as glycogen deposits, have previously been reported in clear-cell neoplasms and some fetal tissues. It remains to be investigated whether the two structures are the same, colocalize UPS components and polysaccharides, and have a role in highly proliferative cells such as fetal and neoplastic cells. We used immunogold electron microscopy and confocal immunofluorescence microscopy to examine human and mouse fetal tissues and human neoplasms. Fetal and neoplastic cells both showed colocalization of polyubiquitinated proteins, 19S and 20S proteasomes, and polysaccharides, both glycogen and chondroitin sulfate, inside cytoplasmic structures showing all distinctive features of PaCSs. Poorly demarcated and/or hybrid (ribosomes admixed) UPS- and glycogen-enriched areas, likely stages in PaCS development, were also seen in some fetal cells, with special reference to those, like primary alveolar pulmonary cells or pancreatic centroacinar cells, having a crucial role in organogenesis. UPS- and glycogen-rich PaCSs developed extensively in clear-cell neoplasms of the kidney, ovary, pancreas, and other organs, as well as, in infantile, development-related tumors replicating fetal patterns, such as choroid plexus papilloma. UPS-mediated, ATP-dependent proteolysis and its potential energy source, glycogen metabolism, may have a crucial, synergic role in embryo-/organogenesis and carcinogenesis.
Keywords: Cytoplasm; Fetus; Glycogen; Humans; Immunohistochemistry; Microscopy, Confocal; Microscopy, Electron, Transmission; Neoplasms; Proteasome Endopeptidase Complex; Ubiquitinated Proteins

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Validation of point-of-care testing for coeliac disease in children in a tertiary hospital in north India. - Singh, Prashant; Wadhwa, Nitya; Chaturvedi, Mona K; Bhatia, Vidyut; Saini, Savita; Tandon, Nikhil; Makharia, Govind K; Maki, Markku; Not, Tarcisio; Phillips, Alan; Bhatnagar, Shinjini (Arch Dis Child, 2014)
OBJECTIVE: Some of the conventional serological tests for coeliac disease (CD) are expensive, time-consuming and not readily available in developing countries, leading to a delay in diagnosis. Recently, point-of-care tests (POCT) have been manufactured and tested in Europe but have not been validated in our setting. We therefore aimed to study the diagnostic accuracy of the POCT 'Biocard' test in diagnosing CD in Indian children. DESIGN: Cross-sectional study. SETTING: Tertiary care centre in north India. PATIENTS: Children, aged 2-18 years, with chronic diarrhoea, short stature or refractory anaemia underwent serological testing for CD with antiendomysial antibodies (AEA), antitissue transglutaminase (tTG) antibodies and Biocard test followed by duodenal biopsy irrespective of serological results. CD was diagnosed with positive AEA and duodenal biopsy showing >grade 2 changes using modified Marsh criteria. Those who were both AEA negative and had normal histology were considered CD negative. RESULTS: Of 319 children who underwent the serological testing, 170 agreed for biopsy. Of these, 110 were diagnosed with CD and 30 were found to be CD negative. Remaining 30 had discordant AEA and histology results and were not included in analysis. Biocard test agreed with 92/110 positive and 27/30 negative diagnoses based on reference tests (83.6% sensitivity and 90% specificity). tTG was found to be 93.8% sensitive and 96.4% specific. CONCLUSIONS: We successfully validated the POCT for CD in our setting. It could be used to increase case detection rates in developing countries with a large undiagnosed CD burden.
Keywords: Adolescent; Celiac Disease; Child; Child, Preschool; Cross-Sectional Studies; Female; Humans; India; Male; Point-of-Care Systems; Sensitivity and Specificity; Serologic Tests; Tertiary Care Centers

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

MYH9-related disease: five novel mutations expanding the spectrum of causative mutations and confirming genotype/phenotype correlations. - De Rocco, Daniela; Zieger, Barbara; Platokouki, Helen; Heller, Paula G; Pastore, Annalisa; Bottega, Roberta; Noris, Patrizia; Barozzi, Serena; Glembotsky, Ana C; Pergantou, Helen; Balduini, Carlo L; Savoia, Anna; et al. (Eur J Med Genet, 2013)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant syndromic disorder caused by mutations in MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (myosin-9). MYH9-RD is characterized by congenital macrothrombocytopenia and typical inclusion bodies in neutrophils associated with a variable risk of developing sensorineural deafness, presenile cataract, and/or progressive nephropathy. The spectrum of mutations responsible for MYH9-RD is limited. We report five families, each with a novel MYH9 mutation. Two mutations, p.Val34Gly and p.Arg702Ser, affect the motor domain of myosin-9, whereas the other three, p.Met847_Glu853dup, p.Lys1048_Glu1054del, and p.Asp1447Tyr, hit the coiled-coil tail domain of the protein. The motor domain mutations were associated with more severe clinical phenotypes than those in the tail domain.
Keywords: Adolescent; Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; Child; Child, Preschool; Exons; Female; Genes, Dominant; Genetic Association Studies; Humans; Male; Middle Aged; Models, Molecular; Molecular Motor Proteins; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Sequence Alignment; Syndrome; Thrombocytopenia; Young Adult

Presence of CTAK/CCL27, MCP-3/CCL7 and LIF in human colostrum and breast milk. - Radillo, Oriano; Norcio, Alessia; Addobbati, Riccardo; Zauli, Giorgio (Cytokine, 2013)
Human colostrum and breast milk are known to contain high levels of cytokines and chemokines, which are thought to contribute to the development of the newborn. The aim of this study was to investigate the difference in the presence and levels of 21 soluble cytokines and chemokines in paired samples of human colostrum (day 2 after delivery) and breast milk (day 4-5 after delivery) by using the multiplex technology. Of the 21 cytokine investigated in 10 pairs of samples, only β-NGF was absent in both colostrum and milk, while INF-α2, SCF and TNF-β were present in colostrum but not in human milk. As a general rule, colostrum contained higher concentrations of cytokines and chemokines with respect to breast milk. The majority of cytokines, detected in colostrum alone or in colostrum and human milk (IL-1α, IL-2Rα, IL-3, IL-16, IL-18, GRO-α, HGF, IFN-α2, M-CSF, MIF, MIG, TNF-β, SDF-1α, TRAIL) have been described in previous studies, while for the first time we describe the presence of additional cytokines either in colostrum alone (SCF) or in both colostrum and breast milk (CTAK/CCL27, MCP-3/CCL7, LIF). Our data confirm and expand previous studies showing that some cytokines/chemokines, which might contribute to the development of the gastro-intestinal and nervous systems, are overexpressed in human colostrum and breast milk, and might contribute to the development of these systems.
Keywords: Adult; Chemokine CCL27; Chemokine CCL7; Chemokines; Colostrum; Cytokines; Female; Humans; Infant, Newborn; Leukemia Inhibitory Factor; Milk, Human

Adverse effects during specific oral tolerance induction: in-hospital "rush" phase. - Barbi, E; Longo, G; Berti, I; Neri, E; Saccari, A; Rubert, L; Matarazzo, L; Montico, M; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach in the treatment of severe food allergies. Different protocols have demonstrated its efficacy. Nevertheless, SOTI is still considered an experimental method and should be limited to highly controlled settings. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of nebulized epinephrine as a first-line treatment of respiratory reactions during in-hospital SOTI for cow's milk allergy. MATERIALS AND METHODS: A retrospective study was conducted by reviewing the medical records of patients admitted for SOTI beginning in 2001. Reactions were classified as mild, moderate and severe on a partially modified Clark scale. Adverse reactions were treated following the International Guidelines with the introduction of nebulized epinephrine for level four reactions. RESULTS: Of 209 patients, 17 were excluded due to the absence of objective reactions. The remaining 192 were classified as follows: Mild Reactions (Clark Scale 1 to 3): 100 patients received either no treatment, oral antihistamines or nebulized steroids; Moderate Reactions (Clark Scale 4): 87 patients treated with nebulized epinephrine and, depending on their symptoms, oral antihistamines, corticosteroids (nebulized, oral or IV) or nebulized beta 2 agonists; Severe Reactions (Clark Scale 5): 5 children, 4 of whom initially underwent one nebulization of epinephrine and eventually required an IM dose. The fifth patient was immediately treated with IM epinephrine due to hypotension. DISCUSSION: adverse reactions during this in-hospital SOTI protocol were frequent but easily manageable. Nebulized epinephrine can play a relevant role in the treatment of respiratory reactions.
Keywords: Administration, Inhalation; Anaphylaxis; Animals; Bronchodilator Agents; Child; Desensitization, Immunologic; Epinephrine; Humans; Milk; Milk Hypersensitivity; Retrospective Studies

Allogeneic hematopoietic stem cell transplantation for Philadelphia-positive acute lymphoblastic leukemia in children and adolescents: a retrospective multicenter study of the Italian Association of Pediatric Hematology and Oncology (AIEOP). - Fagioli, Franca; Zecca, Marco; Rognoni, Carla; Lanino, Edoardo; Balduzzi, Adriana; Berger, Massimo; Messina, Chiara; Favre, Claudio; Rabusin, Marco; Lo Nigro, Luca; Masetti, Riccardo; Prete, Arcangelo; et al. (Biol Blood Marrow Transplant, 2012)
Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) still represents a major challenge. We report the experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) with allogeneic hematopoietic stem cell transplantation (HSCT) in children with Ph+ ALL from 1990 to 2008. Sixty-nine patients received HSCT from either a related (37, 54%) or an unrelated (32, 46%) donor. Twenty-five patients (36%) underwent transplantation before 2000 and 44 (64%) after 2000. Twenty-three patients (33%) received Imatinib mesylate treatment before HSCT and seven (10%) after HSCT. After a median follow-up of 56 months, the overall survival (OS) probability was 51% (95% confidence interval [CI], 38-63), the leukemia-free survival (LFS) was 47% (95% CI, 34-59), transplantation-related mortality (TRM) was 17% (95% CI, 10-30), and relapse incidence (RI) was 36% (95% CI, 26-50). Transplantation in first complete remission, female gender, and lower WBC count at diagnosis were associated with a better LFS in both univariate and multivariate analyses. Patients with p210 transcript had a trend for a worse prognosis compared with those who had the p190 transcript. Our series confirms the role of HSCT in the eradication of Ph+ ALL. Early HSCT is recommended once morphologic remission is obtained.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Benzamides; Child; Child, Preschool; Disease-Free Survival; Drug Administration Schedule; Female; Fusion Proteins, bcr-abl; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Infant; Italy; Male; Philadelphia Chromosome; Piperazines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrimidines; Remission Induction; Retrospective Studies; Secondary Prevention; Transplantation, Homologous; Young Adult

Alteration of liver enzymes is a feature of the MYH9-related disease syndrome. - Pecci, Alessandro; Biino, Ginevra; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Annamaria; Noris, Patrizia; Ramenghi, Ugo; Loffredo, Giuseppe; Fabris, Fabrizio; Momi, Stefania; Magrini, Umberto; Pirastu, Mario; et al. (PLoS One, 2012)
BACKGROUND: MYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia associated with the risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. During the collection of a large case-series of patients with MYH9-RD we noticed several cases with unexplained elevation of liver enzymes. Our aim was to evaluate if the alteration of liver tests is a feature of the MYH9-RD and to define its clinical significance. METHODS AND FINDINGS: Data concerning liver tests, prospectively recorded in the Italian Registry for MYH9-RD, were collected and compared with those of three control populations: patients with autoimmune thrombocytopenia, patients with inherited thrombocytopenias other than MYH9-RD, and the participants to a large epidemiologic survey in an Italian geographic isolate. Thirty-eight of 75 evaluable MYH9-RD patients (50.7%) showed an elevation of ALT and/or AST, and 17 of 63 (27.0%) an increase of GGT. The increases ranged from 1.9 ± 0.7 to 2.7 ± 1.6 fold the upper normal limit. The prevalence of liver test alterations was significantly higher in MYH9-RD patients than in each of the control populations, with odds ratios ranging from 8.2 (95% CIs 2.2-44.8) to 24.7 (14.8-40.8). Clinical follow-up and more detailed liver studies of a subset of patients, including ultrasound liver scan, liver elastography and liver biopsy in one case, did not show any significant structural damage or evolution towards liver insufficiency. CONCLUSIONS: Elevation of liver enzymes is a frequent and previously unrecognized feature of the MYH9-RD syndrome; however, this defect does not appear to have poor prognostic value.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Aged; Aged, 80 and over; Biopsy; Case-Control Studies; Child; Child, Preschool; Demography; Female; Follow-Up Studies; Humans; Immunohistochemistry; Infant; Liver; Liver Function Tests; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Odds Ratio; Syndrome; Young Adult

Clinical and laboratory features of 103 patients from 42 Italian families with inherited thrombocytopenia derived from the monoallelic Ala156Val mutation of GPIbα (Bolzano mutation). - Noris, Patrizia; Perrotta, Silverio; Bottega, Roberta; Pecci, Alessandro; Melazzini, Federica; Civaschi, Elisa; Russo, Sabina; Magrin, Silvana; Loffredo, Giuseppe; Di Salvo, Veronica; Russo, Giovanna; Casale, Maddalena; et al. (Haematologica, 2012)
BACKGROUND: Bernard-Soulier syndrome is a very rare form of inherited thrombocytopenia that derives from mutations in GPIbα, GPIbβ, or GPIX and is typically inherited as a recessive disease. However, some years ago it was shown that the monoallelic c.515C>T transition in the GPIBA gene (Bolzano mutation) was responsible for macrothrombocytopenia in a few Italian patients. DESIGN AND METHODS: Over the past 10 years, we have searched for the Bolzano mutation in all subjects referred to our institutions because of an autosomal, dominant form of thrombocytopenia of unknown origin. RESULTS: We identified 42 new Italian families (103 cases) with a thrombocytopenia induced by monoallelic Bolzano mutation. Analyses of the geographic origin of affected pedigrees and haplotypes indicated that this mutation originated in southern Italy. Although the clinical expression was variable, patients with this mutation typically had a mild form of Bernard-Soulier syndrome with mild thrombocytopenia and bleeding tendency. The most indicative laboratory findings were enlarged platelets and reduced GPIb/IX/V platelet expression; in vitro platelet aggregation was normal in nearly all of the cases. CONCLUSIONS: Our study indicates that monoallelic Bolzano mutation is the most frequent cause of inherited thrombocytopenia in Italy, affecting 20% of patients recruited at our institutions during the last 10 years. Because many people from southern Italy have emigrated during the last century, this mutation may have spread to other countries.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Bernard-Soulier Syndrome; Child; Child, Preschool; Family Health; Female; Heterozygote; Humans; Infant; Italy; Male; Membrane Glycoproteins; Middle Aged; Mutation, Missense; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Genetic; Thrombocytopenia; Thrombopoietin; Tubulin; Young Adult

A coughing spine. - Norbedo, Stefania; Perini, Roberto; Amaddeo, Alessandro (Emerg Med J, 2012)
Keywords: Cervical Vertebrae; Child; Dyspnea; Humans; Male; Mediastinal Emphysema; Spinal Diseases; Subcutaneous Emphysema; Tomography, X-Ray Computed

Defective and excessive immunities in pediatric diseases. - Notarangelo, Luigi Daniele; Tommasini, Alberto (Curr Pharm Des, 2012)
Inflammatory and autoimmune diseases are classically considered as disorders arising from hyper-activation of immunity and hence are treated with drugs that suppress the lymphocyte activation and inflammation. Although this strategy has proven useful to cure symptoms, it rarely can heal the disease and long-term treatments are usually needed. Inflammatory and autoimmune diseases frequently occur also in patients with primary immune deficiency disease, proving that immune hyper-activation may paradoxically arise from defective function of immune genes. In these cases, the phenotype of hyper-activation is believed to reflect the attempts of the immune system to compensate for immune defects. Recent data suggest that similar mechanisms could be involved also in the pathogenesis of some multifactorial disorders, such as Crohn's disease and systemic lupus erythematosus. Based on these considerations, novel therapies could be developed to cure severe autoimmune and inflammatory disorders, not only by aiming to hyper-activation but as well by focusing on the possible underlying immune defects.
Keywords: Autoimmune Diseases; Child; Drug Design; Humans; Immunologic Deficiency Syndromes; Inflammation; Lymphocyte Activation; Severity of Illness Index

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

Gluten-dependent intestinal autoimmune response. - Korponay-Szabó, Ilma Rita; Simon-Vecsei, Zsafia; De Leo, Luigina; Not, Tarcisio (Curr Pharm Des, 2012)
Celiac disease is a multi-systemic autoimmune disease of the small bowel induced by gluten in genetically predisposed subjects. Highly specific and gluten-dependent production of auto-antibodies targeting self-proteins of the transglutaminase family occurs in the intestinal mucosa. These anti-transglutaminase antibodies are found deposited in intestinal and extra-intestinal tissue where they might exert biological effects, together with the intestinal mucosal gliadin-specific T lymphocytes. We conducted a brief review on antitransglutaminase antibodies effects, discussing their roles in the pathogenesis of several clinical manifestations of celiac disease.
Keywords: Animals; Autoantibodies; Celiac Disease; Genetic Predisposition to Disease; Gliadin; Glutens; Humans; Intestinal Mucosa; T-Lymphocytes; Transglutaminases

Influence of age, sex and ethnicity on platelet count in five Italian geographic isolates: mild thrombocytopenia may be physiological. - Biino, Ginevra; Gasparini, Paolo; d'Adamo, Pio; Ciullo, Marina; Nutile, Teresa; Toniolo, Daniela; Sala, Cinzia; Minelli, Cosetta; Gögele, Martin; Balduini, Carlo L (Br J Haematol, 2012)
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Middle Aged; Platelet Count; Reference Values; Sex Distribution; Thrombocytopenia; Young Adult

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

International collaboration as a tool for diagnosis of patients with inherited thrombocytopenia in the setting of a developing country. - Glembotsky, A C; Marta, R F; Pecci, A; De Rocco, D; Gnan, C; Espasandin, Y R; Goette, N P; Negro, F; Noris, P; Savoia, A; Balduini, C L; Molinas, F C; et al. (J Thromb Haemost, 2012)
BACKGROUND: Inherited thrombocytopenias (ITs) are heterogeneous genetic disorders that frequently represent a diagnostic challenge. The requirement of highly specialized tests for diagnosis represents a particular problem in resource-limited settings. To overcome this difficulty, we applied a diagnostic algorithm and developed a collaboration program with a specialized international center in order to increase the diagnostic yield in a cohort of patients in Argentina. METHODS: Based on the algorithm, initial evaluation included collection of clinical data, platelet size, blood smear examination and platelet aggregation tests. Confirmatory tests were performed according to diagnostic suspicion, which included platelet glycoprotein expression, immunofluorescence for myosin-9 in granulocytes and platelet thrombospondin-1 and molecular screening of candidate genes. RESULTS: Thirty-one patients from 14 pedigrees were included; their median age was 32 (4-72) years and platelet count 72 (4-147)×10(9) L(-1). Autosomal dominant inheritance was found in nine (64%) pedigrees; 10 (71%) had large platelets and nine (29%) patients presented with syndromic forms. A definitive diagnosis was made in 10 of 14 pedigrees and comprised MYH9-related disease in four, while classic and monoallelic Bernard-Soulier syndrome, gray platelet syndrome, X-linked thrombocytopenia, thrombocytopenia 2 (ANKRD26 mutation) and familial platelet disorder with predisposition to acute myelogenous leukemia were diagnosed in one pedigree each. CONCLUSIONS: Adoption of an established diagnostic algorithm and collaboration with an expert referral center proved useful for diagnosis of IT patients in the setting of a developing country. This initiative may serve as a model to develop international networks with the goal of improving diagnosis and care of patients with these rare diseases.
Keywords: Adolescent; Adult; Aged; Algorithms; Argentina; Biological Markers; Child; Child, Preschool; Cooperative Behavior; Developing Countries; DNA Mutational Analysis; Feasibility Studies; Female; Flow Cytometry; Fluorescent Antibody Technique; Genetic Predisposition to Disease; Genetic Testing; Health Services Accessibility; Hematologic Tests; Heredity; Humans; International Cooperation; Italy; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Pedigree; Phenotype; Platelet Count; Platelet Function Tests; Predictive Value of Tests; Prognosis; Referral and Consultation; Thrombocytopenia; Thrombospondin 1; Young Adult

MCL1 down-regulation plays a critical role in mediating the higher anti-leukaemic activity of the multi-kinase inhibitor Sorafenib with respect to Dasatinib. - Secchiero, Paola; Melloni, Elisabetta; Voltan, Rebecca; Norcio, Alessia; Celeghini, Claudio; Zauli, Giorgio (Br J Haematol, 2012)
Keywords: Antineoplastic Agents; Benzenesulfonates; Cell Line, Tumor; Down-Regulation; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Protein Kinase Inhibitors; Proto-Oncogene Proteins c-bcl-2; Pyridines; Pyrimidines; Thiazoles

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. - Okada, Yukinori; Sim, Xueling; Go, Min Jin; Wu, Jer-Yuarn; Gu, Dongfeng; Takeuchi, Fumihiko; Takahashi, Atsushi; Maeda, Shiro; Tsunoda, Tatsuhiko; Chen, Peng; Lim, Su-Chi; Wong, Tien-Yin; et al. (Nat Genet, 2012)
Chronic kidney disease (CKD), impairment of kidney function, is a serious public health problem, and the assessment of genetic factors influencing kidney function has substantial clinical relevance. Here, we report a meta-analysis of genome-wide association studies for kidney function-related traits, including 71,149 east Asian individuals from 18 studies in 11 population-, hospital- or family-based cohorts, conducted as part of the Asian Genetic Epidemiology Network (AGEN). Our meta-analysis identified 17 loci newly associated with kidney function-related traits, including the concentrations of blood urea nitrogen, uric acid and serum creatinine and estimated glomerular filtration rate based on serum creatinine levels (eGFRcrea) (P < 5.0 × 10(-8)). We further examined these loci with in silico replication in individuals of European ancestry from the KidneyGen, CKDGen and GUGC consortia, including a combined total of ∼110,347 individuals. We identify pleiotropic associations among these loci with kidney function-related traits and risk of CKD. These findings provide new insights into the genetics of kidney function.
Keywords: Asian Continental Ancestry Group; Blood Urea Nitrogen; Cohort Studies; Creatinine; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Uric Acid

miR-EdiTar: a database of predicted A-to-I edited miRNA target sites. - Laganà, Alessandro; Paone, Alessio; Veneziano, Dario; Cascione, Luciano; Gasparini, Pierluigi; Carasi, Stefania; Russo, Francesco; Nigita, Giovanni; Macca, Valentina; Giugno, Rosalba; Pulvirenti, Alfredo; Shasha, Dennis; et al. (Bioinformatics, 2012)
MOTIVATION: A-to-I RNA editing is an important mechanism that consists of the conversion of specific adenosines into inosines in RNA molecules. Its dysregulation has been associated to several human diseases including cancer. Recent work has demonstrated a role for A-to-I editing in microRNA (miRNA)-mediated gene expression regulation. In fact, edited forms of mature miRNAs can target sets of genes that differ from the targets of their unedited forms. The specific deamination of mRNAs can generate novel binding sites in addition to potentially altering existing ones. RESULTS: This work presents miR-EdiTar, a database of predicted A-to-I edited miRNA binding sites. The database contains predicted miRNA binding sites that could be affected by A-to-I editing and sites that could become miRNA binding sites as a result of A-to-I editing. AVAILABILITY: miR-EdiTar is freely available online at http://microrna.osumc.edu/mireditar. CONTACT: alessandro.lagana@osumc.edu or carlo.croce@osumc.edu SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Adenosine; Binding Sites; Databases, Genetic; Gene Expression Regulation; Humans; Inosine; Internet; MicroRNAs; Nucleic Acid Conformation; RNA Editing

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

New insights in the sugarcane transcriptome responding to drought stress as revealed by superSAGE. - Kido, Éderson Akio; Ferreira Neto, José Ribamar Costa; Silva, Roberta Lane de Oliveira; Pandolfi, Valesca; Guimarães, Ana Carolina Ribeiro; Veiga, Daniela Truffi; Chabregas, Sabrina Moutinho; Crovella, Sergio; Benko-Iseppon, Ana Maria (ScientificWorldJournal, 2012)
In the scope of the present work, four SuperSAGE libraries have been generated, using bulked root tissues from four drought-tolerant accessions as compared with four bulked sensitive genotypes, aiming to generate a panel of differentially expressed stress-responsive genes. Both groups were submitted to 24 hours of water deficit stress. The SuperSAGE libraries produced 8,787,315 tags (26 bp) that, after exclusion of singlets, allowed the identification of 205,975 unitags. Most relevant BlastN matches comprised 567,420 tags, regarding 75,404 unitags with 164,860 different ESTs. To optimize the annotation efficiency, the Gene Ontology (GO) categorization was carried out for 186,191 ESTs (BlastN against Uniprot-SwissProt), permitting the categorization of 118,208 ESTs (63.5%). In an attempt to elect a group of the best tags to be validated by RTqPCR, the GO categorization of the tag-related ESTs allowed the in silico identification of 213 upregulated unitags responding basically to abiotic stresses, from which 145 presented no hits after BlastN analysis, probably concerning new genes still uncovered in previous studies. The present report analyzes the sugarcane transcriptome under drought stress, using a combination of high-throughput transcriptome profiling by SuperSAGE with the Solexa sequencing technology, allowing the identification of potential target genes during the stress response.
Keywords: Droughts; Gene Expression Profiling; Heat-Shock Response; Plant Proteins; Saccharum; Transcriptome

Pathergy as a cause of false-positive tuberculin skin test. - Pastore, Serena; Naviglio, Samuele; Ventura, Alessandro (Pediatr Infect Dis J, 2012)
Keywords: Adolescent; Behcet Syndrome; False Positive Reactions; Female; Humans; Hypersensitivity; Needles; Skin; Skin Tests; Tuberculin Test; Tuberculosis, Gastrointestinal

Potential role of TRAIL in the management of autoimmune diabetes mellitus. - Bernardi, Stella; Norcio, Alessia; Toffoli, Barbara; Zauli, Giorgio; Secchiero, Paola (Curr Pharm Des, 2012)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease, due to the immune-mediated destruction of pancreatic β-cells, whose incidence has been steadily increasing during the last decades. Insulin replacement therapy can treat T1DM, which, however, is still associated with substantial morbidity and mortality. For this reason, great effort is being put into developing strategies that could eventually prevent and/or cure this disease. These strategies are mainly focused on blocking the immune system from attacking β-cells together with functional islet restoration either by regeneration or transplantation. Recent experimental evidences suggest that TNFrelated apoptosis-inducing ligand (TRAIL), which is an immune system modulator protein, could represent an interesting candidate for the cure for T1DM and/or its complications. Here we review the evidences on the potential role of TRAIL in the management of T1DM.
Keywords: Animals; Autoimmunity; Diabetes Mellitus, Type 1; Humans; Hypoglycemic Agents; Insulin; Insulin-Secreting Cells; Islets of Langerhans; TNF-Related Apoptosis-Inducing Ligand

Relation between maternal thrombophilia and stillbirth according to causes/associated conditions of death. - Monari, F; Alberico, S; Avagliano, L; Cetin, I; Cozzolino, S; Gargano, G; Marozio, L; Mecacci, F; Neri, I; Tranquilli, A L; Venturini, P; Facchinetti, F (Early Hum Dev, 2012)
OBJECTIVE: To investigate maternal thrombophilia in cases of Stillbirth (SB), also an uncertain topic because most case series were not characterised for cause/associated conditions of death. STUDY DESIGN: In a consecutive, prospective, multicentre design, maternal DNA was obtained in 171 cases of antenatal SB and 326 controls (uneventful pregnancy at term, 1:2 ratio). Diagnostic work-up of SB included obstetric history, neonatologist inspection, placenta histology, autopsy, microbiology/chromosome evaluations. Results audited in each centre were classified by two of us by using CoDAC. Cases were subdivided into explained SB where a cause of death was identified and although no defined cause was detected in the remnants, 64 cases found conditions associated with placenta-vascular disorders (including preeclampsia, growth restriction and placenta abruption - PVD). In the remnant 79 cases, no cause of death or associated condition was found. Antithrombin activity, Factor V Leiden, G20210A Prothrombin mutation (FII mutation) and acquired thrombophilia were analysed. RESULTS: Overall, the presence of a thrombophilic defect was significantly more prevalent in mothers with SBs compared to controls. In particular, SB mothers showed an increased risk of carrying Factor II mutation (OR=3.2, 95% CI: 1.3-8.3, p=0.01), namely in unexplained cases. Such mutation was significantly associated also with previous SB (OR=8.9, 95%CI 1.2-70.5). At multiple logistic regression, Factor II mutation was the only significantly associated variable with SB (adj OR=3.8, 95% CI: 1.3-13.5). CONCLUSION: These data suggest that Factor II mutation is the only condition specifically associated with unexplained SB and could represents a risk of recurrence. PVD-associated condition is unrelated to thrombophilia.
Keywords: Adult; Case-Control Studies; Cause of Death; Female; Fetal Diseases; Fetal Mortality; Humans; Infant, Newborn; Male; Placenta Diseases; Pre-Eclampsia; Pregnancy; Pregnancy Complications, Hematologic; Socioeconomic Factors; Stillbirth; Thrombophilia; Young Adult

Sedation with intranasal midazolam of Angolan children undergoing invasive procedures. - Kawanda, Lumana; Capobianco, Ivan; Starc, Meta; Felipe, Daniel; Zanon, Davide; Barbi, Egidio; Munkela, Nadine; Rodrigues, Verónica; Malundo, Lúis; Not, Tarcisio (Acta Paediatr, 2012)
AIM: Ambulatory surgery is a daily requirement in poor countries, and limited means and insufficient trained staff lead to the lack of attention to the patient's pain. Midazolam is a rapid-onset, short-acting benzodiazepine which is used safely to reduce pain in children. We evaluated the practicability of intranasal midazolam sedation in a suburban hospital in Luanda (Angola), during the surgical procedures. METHODS: Intranasal midazolam solution was administered at a dose of 0.5 mg/kg. Using the Ramsay's reactivity score, we gave a score to four different types of children's behaviour: moaning, shouting, crying and struggling, and the surgeon evaluated the ease of completing the surgical procedure using scores from 0 (very easy) to 3 (managing with difficulty). RESULTS: Eighty children (median age, 3 years) were recruited, and 140 surgical procedures were performed. Fifty-two children were treated with midazolam during 85 procedures, and 28 children were not treated during 55 procedures. We found a significant difference between the two groups on the shouting, crying and struggling parameters (p < 0.001). The mean score of the ease of completing the procedures was significantly different among the two groups (p < 0.0001). CONCLUSION: These results provide a model of procedural sedation in ambulatory surgical procedures in poor countries, thus abolishing pain and making the surgeon's job easier.
Keywords: Administration, Intranasal; Adolescent; Ambulatory Surgical Procedures; Angola; Child; Child Behavior; Child, Preschool; Conscious Sedation; Crying; Female; Humans; Hypnotics and Sedatives; Infant; Male; Midazolam; Prospective Studies

SOCS1 is significantly up-regulated in Nutlin-3-treated p53wild-type B chronic lymphocytic leukemia (B-CLL) samples and shows an inverse correlation with miR-155. - di Iasio, Maria Grazia; Norcio, Alessia; Melloni, Elisabetta; Zauli, Giorgio (Invest New Drugs, 2012)
The basal SOCS1 mRNA levels were significantly lower in p53(mutated) BJAB and MAVER leukemic cell lines with respect to p53(wild-type) SKW6.4 and JVM-2 leukemic cell lines, p53(wild-type) primary B chronic lymphocytic leukemia (B-CLL) cells and primary normal peripheral blood mononuclear cells (PBMC). Moreover, the MDM2 small molecule inhibitor Nutlin-3 significantly increased the levels of SOCS1 mRNA in both primary p53(wild-type) B-CLL cells as well as in p53(wild-type) B leukemic cell lines, but not in p53(mutated) B leukemic cell lines nor in primary PBMC. Of note, a significant inverse correlation was observed between SOCS1 mRNA and miR-155 levels in Nutlin-3-treated primary B-CLL cells and PBMC, suggesting that the miRNA-155/SOCS1 axis represents a potentially important therapeutic target of Nutlin-3 in B-CLL.
Keywords: Cell Line, Tumor; Cells, Cultured; Down-Regulation; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Leukocytes, Mononuclear; MicroRNAs; Piperazines; Suppressor of Cytokine Signaling Proteins; Tumor Suppressor Protein p53; Up-Regulation

The active Zot domain (aa 288-293) increases ZO-1 and myosin 1C serine/threonine phosphorylation, alters interaction between ZO-1 and its binding partners, and induces tight junction disassembly through proteinase activated receptor 2 activation. - Goldblum, Simeon E; Rai, Usha; Tripathi, Amit; Thakar, Manjusha; De Leo, Luigina; Di Toro, Nicola; Not, Tarcisio; Ramachandran, Rithwik; Puche, Adam C; Hollenberg, Morley D; Fasano, Alessio (FASEB J, 2011)
Vibrio cholerae-derived zonula occludins toxin (Zot) is a multifunctional protein that reversibly disassembles intestinal tight junctions (tjs). Zot structure-function analysis has mapped this activity to aa 288-293, named AT1002. AT1002 reduced transepithelial electrical resistance across rat small intestine, ex vivo, as did Zot and its processed mature form, ΔG. AT1002 increased in vivo permeability to sugar tracers, whereas scrambled control peptides did not. Binding and barrier assays in proteinase activated receptor (PAR)(2)-expressing and PAR(2)-null cells established AT1002 activity to be PAR(2) dependent. Coincident with the increased intestinal permeability, confocal microscopy of AT1002-exposed rat intestinal IEC6 cells revealed displacement of ZO-1 and occludin from intercellular boundaries. In coimmunoprecipitation assays, AT1002 decreased ZO-1-occludin and ZO-1-claudin 1 interactions coincident with PKCα-dependent ZO-1 serine/threonine phosphorylation. Further, AT1002 increased serine phosphorylation of myosin 1C and, at the same time, transiently diminished its association with ZO-1. The COOH-terminal domain of ZO-1 was required for its association with myosin 1C. These data indicate that the NH(2)-terminal portion of active Zot contains a PAR(2)-activating motif, FCIGRL, that increases PKCα-dependent ZO-1 and myosin 1C serine/threonine phosphorylation. These modifications provoke selective disengagement of ZO-1 from its binding partners, occludin, claudin 1, and myosin 1C, coincident with opening of tjs.
Keywords: Amino Acid Sequence; Animals; Caco-2 Cells; Cell Line; Cells, Cultured; Cholera Toxin; Epithelial Cells; Humans; Immunoblotting; Male; Membrane Proteins; Mice; Mice, Inbred BALB C; Molecular Sequence Data; Myosins; Oligopeptides; Phosphoproteins; Phosphorylation; Protein Binding; Protein Kinase C-alpha; Rats; Rats, Wistar; Receptor, PAR-2; RNA Interference; Serine; Threonine; Tight Junctions; Zonula Occludens-1 Protein

Ages of celiac disease: from changing environment to improved diagnostics. - Tommasini, Alberto; Not, Tarcisio; Ventura, Alessandro (World J Gastroenterol, 2011)
From the time of Gee's landmark writings, the recent history of celiac disease (CD) can be divided into many ages, each driven by a diagnostic advance and a deeper knowledge of disease pathogenesis. At the same time, these advances were paralleled by the identification of new clinical patterns associated with CD and by a continuous redefinition of the prevalence of the disease in population. In the beginning, CD was considered a chronic indigestion, even if the causative food was not known; later, the disease was proven to depend on an intolerance to wheat gliadin, leading to typical mucosal changes in the gut and to a malabsorption syndrome. This knowledge led to curing the disease with a gluten-free diet. After the identification of antibodies to gluten (AGA) in the serum of patients and the identification of gluten-specific lymphocytes in the mucosa, CD was described as an immune disorder, resembling a chronic "gluten infection". The use of serological testing for AGA allowed identification of the higher prevalence of this disorder, revealing atypical patterns of presentation. More recently, the characterization of autoantibodies to endomysium and to transglutaminase shifted the attention to a complex autoimmune pathogenesis and to the increased risk of developing autoimmune disorders in untreated CD. New diagnostic assays, based on molecular technologies, will introduce new changes, with the promise of better defining the spectrum of gluten reactivity and the real burden of gluten related-disorders in the population. Herein, we describe the different periods of CD experience, and further developments for the next celiac age will be proposed.
Keywords: Autoantibodies; Celiac Disease; Diet, Gluten-Free; Gliadin; Glutens; History, 19th Century; History, 20th Century; History, 21st Century; History, Ancient; History, Medieval; Humans; Transglutaminases

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Childhood chronic anterior uveitis associated with vernal keratoconjunctivitis (VKC): successful treatment with topical tacrolimus. Case series. - Taddio, Andrea; Cimaz, Rolando; Caputo, Roberto; de Libero, Cinzia; Di Grande, Laura; Simonini, Gabriele; Mori, Francesca; Novembre, Elio; Pucci, Neri (Pediatr Rheumatol Online J, 2011)
Uveitis treatment involves topical corticosteroids along with cycloplegic-mydriatics. Particularly severe cases may require systemic corticosteroids and immunosuppressive drugs. Vernal keratoconjunctivitis (VKC) treatment consists of a brief period of topical corticosteroids and/or cyclosporine. In patients refractory to traditional treatment, the use of 0.1% topical ophtalmic FK- 506 (tacrolimus) ointment has been occasionally reported.This is the first report of the coexistence of uveitis and VKC. The documented response to topical tacrolimus eyedrop of uveitis and VKC is also of interest, in particular since to our knowledge there are no published reports on its clinical use in uveitis.

Clinical and genetic aspects of Bernard-Soulier syndrome: searching for genotype/phenotype correlations. - Savoia, Anna; Pastore, Annalisa; De Rocco, Daniela; Civaschi, Elisa; Di Stazio, Mariateresa; Bottega, Roberta; Melazzini, Federica; Bozzi, Valeria; Pecci, Alessandro; Magrin, Silvana; Balduini, Carlo L; Noris, Patrizia (Haematologica, 2011)
BACKGROUND: Bernard-Soulier syndrome is a severe bleeding disease due to a defect of GPIb/IX/V, a platelet complex that binds the von Willebrand factor. Due to the rarity of the disease, there are reports only on a few cases compromising any attempt to establish correlations between genotype and phenotype. In order to identify any associations, we describe the largest case series ever reported, which was evaluated systematically at the same center. DESIGN AND METHODS: Thirteen patients with the disease and seven obligate carriers were enrolled. We collected clinical aspects and determined platelet features, including number and size, expression of membrane glycoproteins, and ristocetin induced platelet aggregation. Mutations were identified by direct sequencing of the GP1BA, GP1BB, and GP9 genes and their effect was shown by molecular modeling analyses. RESULTS: Patients all had a moderate thrombocytopenia with giant platelets and a bleeding tendency whose severity varied among individuals. Consistent with expression levels of GPIbα always lower than 10% of control values, platelet aggregation was absent or severely reduced. Homozygous mutations were identified in the GP1BA, GP1BB and GP9 genes; six were novel alterations expected to destabilize the conformation of the respective protein. Except for obligate carriers of a GP9 mutation with a reduced GPIb/IX/V expression and defective aggregation, all the other carriers had no obvious anomalies. CONCLUSIONS: Regardless of mutations identified, the patients' bleeding diathesis did not correlate with thrombocytopenia, which was always moderate, and platelet GPIbα expression, which was always severely impaired. Obligate carriers had features similar to controls though their GPIb/IX/V expression showed discrepancies. Aware of the limitations of our cohort, we cannot define any correlations. However, further investigations should be encouraged to better understand the causes of this rare and underestimated disease.
Keywords: Adolescent; Adult; Amino Acid Sequence; Bernard-Soulier Syndrome; Blood Platelets; Cell Shape; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Markers; Hemorrhage; Homozygote; Humans; Italy; Male; Membrane Glycoproteins; Middle Aged; Molecular Sequence Data; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Point Mutation; Polymerase Chain Reaction; Ristocetin; Thrombocytopenia; von Willebrand Factor; Young Adult

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Compliance with the gluten-free diet: the role of locus of control in celiac disease. - Bellini, Anna; Zanchi, Chiara; Martelossi, Stefano; Di Leo, Grazia; Not, Tarcisio; Ventura, Alessandro (J Pediatr, 2011)
OBJECTIVES: To verify whether subjects with celiac disease (CD) have a different locus of control (LoC) compared with healthy subjects, and to evaluate the relationship between LoC and compliance with a prescribed gluten-free diet (GFD) and quality of life (QoL). STUDY DESIGN: We studied 156 subjects on a GFD (mean age, 10 years) and 353 healthy controls (mean age, 12 years). All subjects completed tests on the Nowicki-Strickland Locus of Control Scale; the subjects with CD also completed a questionnaire to measure compliance with dietary treatment and the disease's impact on QoL. RESULTS: There was no difference in LoC values between patients with CD and controls. Subjects with CD with good dietary compliance had a more internal LoC compared with those who were not compliant (P = .01). Patients who reported a satisfactory QoL had a more internal LoC compared with those who reported negative affects on QoL due to CD (P = .01). CONCLUSIONS: Our study confirms the usefulness of the LoC concept for identifying those patients who might be at risk for dietary transgression. Given the enhanced, psychological, and social well being that can result from adherence to a GFD, educational and psychological support can help internalize the LoC in those patients at risk for dietary transgression.
Keywords: Adolescent; Age Factors; Case-Control Studies; Celiac Disease; Child; Diet, Gluten-Free; Female; Humans; Internal-External Control; Italy; Male; Patient Compliance; Quality of Life

Cryptic genetic gluten intolerance revealed by intestinal antitransglutaminase antibodies and response to gluten-free diet. - Not, Tarcisio; Ziberna, Fabiana; Vatta, Serena; Quaglia, Sara; Martelossi, Stefano; Villanacci, Vincenzo; Marzari, Roberto; Florian, Fiorella; Vecchiet, Monica; Sulic, Ana-Marija; Ferrara, Fortunato; Bradbury, Andrew; et al. (Gut, 2011)
BACKGROUND AND OBJECTIVE: Antitransglutaminase (anti-TG2) antibodies are synthesised in the intestine and their presence seems predictive of future coeliac disease (CD). This study investigates whether mucosal antibodies represent an early stage of gluten intolerance even in the absence of intestinal damage and serum anti-TG2 antibodies. METHODS: This study investigated 22 relatives of patients with CD genetically predisposed to gluten intolerance but negative for both serum anti-TG2 antibodies and intestinal abnormalities. Fifteen subjects were symptomatic and seven were asymptomatic. The presence of immunoglobulin A anti-TG2 antibodies in the intestine was studied by creating phage-antibody libraries against TG-2. The presence of intestinal anti-TG2 antibodies was compared with the serum concentration of the intestinal fatty acid-binding protein (I-FABP), a marker for early intestinal mucosal damage. The effects of a 12-month gluten-free diet on anti-TG2 antibody production and the subjects' clinical condition was monitored. Twelve subjects entered the study as controls. RESULTS: The intestinal mucosa appeared normal in 18/22; 4 had a slight increase in intraepithelial lymphocytes. Mucosal anti-TG2 antibodies were isolated in 15/22 subjects (68%); in particular symptomatic subjects were positive in 13/15 cases and asymptomatic subjects in 2/7 cases (p=0.01). No mucosal antibodies were selected from the controls' biopsies. There was significant correlation between the presence of intestinal anti-TG2 antibodies and positive concentrations of I-FABP (p=0.0008). After a gluten-free diet, 19/22 subjects underwent a second intestinal biopsy, which showed that anti-TG2 antibodies had disappeared in 12/15 (p=0.002), while I-FABP decreased significantly (p<0.0001). The diet resolved both extraintestinal and intestinal symptoms. CONCLUSIONS: A new form of genetic-dependent gluten intolerance has been described in which none of the usual diagnostic markers is present. Symptoms and intestinal anti-TG2 antibodies respond to a gluten free-diet. The detection of intestinal anti-TG2 antibodies by the phage-antibody libraries has an important diagnostic and therapeutic impact for the subjects with gluten-dependent intestinal or extraintestinal symptoms. Clinical trial number NCT00677495.
Keywords: Adolescent; Adult; Antibodies, Anti-Idiotypic; Asymptomatic Diseases; Celiac Disease; Child; Child, Preschool; Diet, Gluten-Free; Fatty Acid-Binding Proteins; Female; Genetic Predisposition to Disease; GTP-Binding Proteins; Health Status; Humans; Intestinal Mucosa; Male; Middle Aged; Peptide Library; Transglutaminases; Young Adult

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Gastrointestinal Foxp3 expression in normal, inflammatory and neoplastic conditions. - Villanacci, Vincenzo; Not, Tarcisio; Nascimbeni, Riccardo; Ferrara, Fortunato; Tommasini, Alberto; Manenti, Stefania; Antonelli, Elisabetta; Bassotti, Gabrio (Pathology, 2011)
BACKGROUND: Foxp3(+) regulatory T lymphocytes (T-regs) represent an important regulatory cell subset in inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract. METHODS: Inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract (189 cases) were studied with the evaluation of Foxp3 regulatory T cells based on immunohistochemistry. RESULTS: Few Foxp3(+) cells were found in controls and inflammatory conditions (oesophagitis, gastritis, coeliac disease, inflammatory bowel disease); in preneoplastic and neoplastic conditions the number of Foxp3(+) cells was significatively increased. CONCLUSIONS: In normal conditions the number of mucosal lymphocytes is very low throughout the gastro-intestinal tract; in active coeliac disease patients or on a gluten-free diet, only a slight increase in Foxp3(+) cells may be found. Gastrointestinal cancers are associated with higher Foxp3(+) cell proportion, compared with microscopically normal tissue and with precancerous conditions. However, it is uncertain whether the increase in these regulatory cells is a cause or a consequence of tumour progression.
Keywords: Adult; Aged; Celiac Disease; Cell Count; Disease Progression; Esophagitis; Female; Forkhead Transcription Factors; Gastric Mucosa; Gastritis; Humans; Inflammatory Bowel Diseases; Lymphocytes; Male; Middle Aged; Precancerous Conditions; Stomach Diseases; Stomach Neoplasms; Young Adult

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Glutamine-enriched nutrition does not reduce mucosal morbidity or complications after stem-cell transplantation for childhood malignancies: a prospective randomized study. - Uderzo, Cornelio; Rebora, Paola; Marrocco, Emanuela; Varotto, Stefania; Cichello, Francesca; Bonetti, Maurizio; Maximova, Natalia; Zanon, Davide; Fagioli, Franca; Nesi, Francesca; Masetti, Riccardo; Masetti, Roberto; et al. (Transplantation, 2011)
BACKGROUND: Intravenous glutamine-enriched solution seems to be effective in posttransplant period in decreasing the severity and duration of mucositis. The aim of this randomized study was to determine the benefit of glutamine supplementation both on mucosal morbidity and in posttransplant associated complications. METHODS: Children undergoing allogeneic hematopoietic stem-cell transplantation (HSCT) for malignant hematological diseases were randomly assigned to standard total parenteral nutrition (S-TPN) or glutamine-enriched (GE)-TPN solution consisting of 0.4 g/kg/day of l-alanine-glutamine dipeptide. This treatment started on the day of HSCT and ended when the patients could orally cover more than 50% of their daily energy requirements. The severity and the rate of post-HSCT mucositis were based on World Health Organization criteria. All the analyses were conducted on intention-to-treat principle. RESULTS: One hundred twenty consecutive patients (83 men; median age, 8.1 years) were enrolled. The mean duration of treatment was 23.5 and 23 days in the two treatment arms. The mean calorie intake was 1538 kcal/d in the S-TPN group and 1512 kcal/d in GE-TPN group. All patients were well nourished before and after HSCT. Mucositis occurred in 91.4% and 91.7% of patients in S-TPN and GE-TPN arm, respectively (P=0.98). Odds ratio adjusted by type of HSCT was 0.98 (95% confidence interval, 0.26-2.63). Type and duration of analgesic treatment, clinical outcome (engraftment, graft versus host disease, early morbidity, and mortality, relapse rate up to 180 days post-HSCT) were not significantly different in the two treatment arms. CONCLUSION: GE-TPN solution does not affect mucositis and outcome in well-nourished HSCT allogeneic patients.
Keywords: Adolescent; Analgesia; Child; Child, Preschool; Double-Blind Method; Female; Glutamine; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Mucositis; Mucous Membrane; Neoplasms; Odds Ratio; Parenteral Nutrition; Prospective Studies; Recurrence; Stem Cells; Treatment Outcome

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia

Phospholipase C-β3 is a key modulator of IL-8 expression in cystic fibrosis bronchial epithelial cells. - Bezzerri, Valentino; d'Adamo, Pio; Rimessi, Alessandro; Lanzara, Carmen; Crovella, Sergio; Nicolis, Elena; Tamanini, Anna; Athanasakis, Emmanouil; Tebon, Maela; Bisoffi, Giulia; Drumm, Mitchell L; Knowles, Michael R; et al. (J Immunol, 2011)
Respiratory insufficiency is the major cause of morbidity and mortality in patients affected by cystic fibrosis (CF). An excessive neutrophilic inflammation, mainly orchestrated by the release of IL-8 from bronchial epithelial cells and amplified by chronic bacterial infection with Pseudomonas aeruginosa, leads to progressive tissue destruction. The anti-inflammatory drugs presently used in CF patients have several limitations, indicating the need for identifying novel molecular targets. To address this issue, we preliminarily studied the association of 721 single nucleotide polymorphisms from 135 genes potentially involved in signal transduction implicated in neutrophil recruitment in a cohort of F508del homozygous CF patients with either severe or mild progression of lung disease. The top ranking association was found for a nonsynonymous polymorphism of the phospholipase C-β3 (PLCB3) gene. Studies in bronchial epithelial cells exposed to P. aeruginosa revealed that PLCB3 is implicated in extracellular nucleotide-dependent intracellular calcium signaling, leading to activation of the protein kinase Cα and Cβ and of the nuclear transcription factor NF-κB p65. The proinflammatory pathway regulated by PLCB3 acts by potentiating the Toll-like Receptors' signaling cascade and represents an interesting molecular target to attenuate the excessive recruitment of neutrophils without completely abolishing the inflammatory response.
Keywords: Adenosine Triphosphate; Calcium; Cell Line, Transformed; Cystic Fibrosis; Enzyme Activation; Epithelial Cells; Gene Expression; Gene Frequency; Genotype; Green Fluorescent Proteins; Host-Pathogen Interactions; Humans; Interleukin-8; Isoenzymes; Lung Diseases; Microscopy, Fluorescence; Phospholipase C beta; Polymorphism, Single Nucleotide; Protein Kinase C; Protein Kinase C beta; Pseudomonas aeruginosa; RNA Interference; Toll-Like Receptors; Transcription Factor RelA

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

Serum anti-Müllerian hormone as a predictive marker of polycystic ovarian syndrome. - Parco, Sergio; Novelli, Caterina; Vascotto, Fulvia; Princi, Tanja (Int J Gen Med, 2011)
BACKGROUND: The anti-Müllerian hormone (AMH) is a dimeric protein secreted by the female ovaries and has two fundamental roles in follicle genesis. It delays the entrance of the primordial follicle into the pool of follicles in growth and diminishes the sensitivity of the ovarian follicle towards follicle-stimulating hormone (FSH). The purpose of this work was to study the AMH (nv 2.0-6.8 ng/mL) as a marker during assisted reproductive technology (ART), in order to identify cases of infertility due to polycystic ovarian syndrome (PCOS). This syndrome affects 10% of women with infertility problems, and a new biological marker could be useful to general practitioners of internal medicine to help generate the suspicion of PCOS so that they can refer the patient to the gynecologist for confirmation. METHODS: This study enrolled 236 patients aged 26-46 years undergoing assisted reproductive technology at the Institute for Maternal and Child Health, Trieste, Italy. On the third day of the ovarian cycle, the patients were given doses of AMH, FSH, and luteinizing hormone (LH, in cases of AMH < 2.0-6.8 ng/mL). A control pelvic ultrasound was also carried out. RESULTS: We identified 57 patients who were starting in vitro fertilization or embryo transfer with AMH values within the normal range (3.64 ± 1.51 ng/mL), 77 with values below normal (1.38 ± 0.32 ng/mL), and 96 cases with undetectable values of AMH. Six patients had very high AMH levels (10.0 ± 2.28 ng/mL) and, of these, five were found to have PCOS on pelvic ultrasound examination (P < 0.05). We also found inverse correlations between AMH levels and age (r = -0.52) and between AMH and FSH levels (r = -0.32). CONCLUSION: In clinical practice it is common to encounter patients who turn to medicine in search of a cure for female infertility. In our experience, AMH two or three times the normal amount (10 ± 2.28 ng/mL), is a good indication of PCOS and infertility.

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Tag-single nucleotide polymorphism-based human leukocyte antigen genotyping in celiac disease patients from northeastern Italy. - Vatta, Serena; Fabris, Annalisa; Segat, Ludovica; Not, Tarcisio; Crovella, Sergio (Hum Immunol, 2011)
We genotyped celiac disease (CD)-associated haplotypes DQ2.5, DQ8, DQ2.2, and DQ7 in 1005 CD patients from North Eastern Italy using a Tag-single nucleotide polymorphism (SNPs) approach and real time PCR platform, checking the accuracy and reliability of the method and comparing it to traditional PCR-SSP. Only 14 of 2010 chromosomes analyzed (0.7%) showed discrepancies between the Tag-SNPs real-time polymerase chain reaction (PCR) method and the PCR-single-strand polymorphism (SSP) technique, indicating a high sensitivity and specificity (ranging from 0.987 to 1 and from 0.998 to 0.999, respectively) for tagging with respect to corresponding human leukocyte antigen (HLA) alleles identified by PCR-SSP. Moreover, the overall cost of the Tag-SNPs HLA typing method was low (3 to 4 €/sample instead of 35 to 70 €/sample with commercial kits), making it suitable for mass screenings. Hence, we believe that the Tag-SNPs HLA typing could be used to complement or replace classic HLA typing in at high-risk groups, for research purposes and eventually in population screening programs.
Keywords: Adolescent; Adult; Aged; Celiac Disease; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Mass Screening; Middle Aged; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Reproducibility of Results; Reverse Transcriptase Polymerase Chain Reaction; Sensitivity and Specificity

Therapeutic approaches in the treatment of juvenile dermatomyositis in patients with recent-onset disease and in those experiencing disease flare: an international multicenter PRINTO study. - Hasija, Rachana; Pistorio, Angela; Ravelli, Angelo; Demirkaya, Erkan; Khubchandani, Raju; Guseinova, Dinara; Malattia, Clara; Canhao, Helena; Harel, Liora; Foell, Dirk; Wouters, Carine; De Cunto, Carmen; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To evaluate response to therapy over a 24-month period in a large prospective international cohort of patients with juvenile dermatomyositis (DM). METHODS: The study included 145 patients with recent-onset juvenile DM and 130 juvenile DM patients experiencing disease flare, all of whom were <18 years old. Disease activity parameters and therapeutic approaches in 4 geographic areas were analyzed at baseline and at 6, 12, and 24 months. Response was assessed according to the Pediatric Rheumatology International Trials Organization (PRINTO) juvenile DM response criteria, and data were reported "as observed" and in the intent-to-treat (ITT) population. RESULTS: Patients with recent-onset juvenile DM at baseline had higher baseline disease activity and greater improvement over 24 months when compared to juvenile DM patients experiencing disease flare at baseline. Methotrexate (MTX) or high-dose corticosteroids were administered more frequently to patients with recent-onset juvenile DM, compared to juvenile DM patients experiencing disease flare, who were more likely to receive cyclosporine. Compared to patients from Western and Eastern Europe, a higher proportion of patients from South and Central America and North America received pulse steroids, and the average steroid dosage was higher in the North American and South and Central American patients. The use of MTX was similar in all 4 regions, while cyclosporin A was more frequently used in Western Europe. In the "as observed" analysis, 57.9% of the patients with recent-onset juvenile DM and 36.4% of the patients experiencing disease flare (P<0.001) reached at least a 70% response by PRINTO criteria at 6 months; these proportions had increased at month 24 to 78.4% and 51.2%, respectively (P<0.001). Corresponding results of the ITT analysis were much lower, with only one-third of the patients able to maintain the initial assigned therapy over 24 months. CONCLUSION: Patients with recent-onset juvenile DM are more likely to achieve significant clinical improvement over 24 months, when compared to patients experiencing flares of juvenile DM. Internationally, various therapeutic approaches are used to treat this disease.
Keywords: Adolescent; Adrenal Cortex Hormones; Child; Dermatologic Agents; Dermatomyositis; Female; Humans; Longitudinal Studies; Male; Methotrexate; Prospective Studies; Treatment Outcome

Use of zidovudine-sparing HAART in pregnant HIV-infected women in Europe: 2000-2009. - Tariq, Shema; Townsend, Claire L; Cortina-Borja, Mario; Duong, Trinh; Elford, Jonathan; Thorne, Claire; Tookey, Pat A (J Acquir Immune Defic Syndr, 2011)
BACKGROUND: Increasing numbers of women in resource-rich settings are prescribed zidovudine (ZDV)-sparing highly active antiretroviral therapy (HAART) in pregnancy. We compare ZDV-sparing with ZDV-containing HAART in relation to maternal viral load at delivery, mother-to-child transmission (MTCT) of HIV, and congenital abnormality. METHODS: This is an analysis of data from the National Study of HIV in Pregnancy and Childhood and the European Collaborative Study. Data on 7573 singleton births to diagnosed HIV-infected women between January 2000 and June 2009 were analyzed. Logistic regression models were fitted to estimate adjusted odds ratios (AORs). RESULTS: Overall, 15.8% (1199 of 7573) of women received ZDV-sparing HAART, with increasing use between 2000 and 2009 (P < 0.001). Nearly a fifth (18.4%) of women receiving ZDV-sparing HAART in pregnancy had a detectable viral load at delivery compared with 28.6% of women on ZDV-containing HAART [AOR 0.90; 95% confidence interval (CI): 0.72 to 1.14, P = 0.4]. MTCT rates were 0.8% and 0.9% in the ZDV-sparing and ZDV-containing groups, respectively (AOR 1.81; 95% CI: 0.77 to 4.26, P = 0.2). The congenital abnormality rate was the same in both groups (2.7%, AOR 0.98; 95% CI: 0.66 to 1.45, P = 0.9), with no significant difference between the groups in a subanalysis of pregnancies with first trimester HAART exposure (AOR 0.79; 95% CI: 0.48 to 1.30, P = 0.4). CONCLUSIONS: We found no difference in risk of detectable viral load at delivery, MTCT, or congenital abnormality when comparing ZDV-sparing with ZDV-containing HAART. With increasing use of ZDV-sparing HAART, continued monitoring of pregnancy outcomes and long-term consequences of in utero exposure to these drugs is required.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Europe; Female; HIV Infections; Humans; Infant; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious; Retrospective Studies; Time Factors; Viral Load; Zidovudine

Abatacept improves health-related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis. - Ruperto, Nicolino; Lovell, Daniel J; Li, Tracy; Sztajnbok, Flavio; Goldenstein-Schainberg, Claudia; Scheinberg, Morton; Penades, Inmaculada Calvo; Fischbach, Michael; Alcala, Javier Orozco; Hashkes, Philip J; Hom, Christine; Jung, Lawrence; et al. (Arthritis Care Res (Hoboken), 2010)
OBJECTIVE: To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA). METHODS: In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to ≥1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatology Pediatric 30 criteria for improvement (defined "responders") were randomized to abatacept or placebo (plus MTX) in the 6-month double-blind withdrawal period (period B). HRQOL assessments included 15 Child Health Questionnaire (CHQ) health concepts plus the physical (PhS) and psychosocial summary scores (PsS), pain (100-mm visual analog scale), the Children's Sleep Habits Questionnaire, and a daily activity participation questionnaire. RESULTS: A total of 190 subjects from period A and 122 from period B were eligible for analysis. In period A, there were substantial improvements across all of the CHQ domains (greatest improvement was in pain/discomfort) and the PhS (8.3 units) and PsS (4.3 units) with abatacept. At the end of period B, abatacept-treated subjects had greater improvements versus placebo in all domains (except behavior) and both summary scores. Similar improvement patterns were seen with pain and sleep. For participation in daily activities, an additional 2.6 school days/month and 2.3 parents' usual activity days/month were gained in period A responders with abatacept, and further gains were made in period B (1.9 versus 0.9 [P = 0.033] and 0.2 versus -1.3 [P = 0.109] school days/month and parents' usual activity days/month, respectively, in abatacept- versus placebo-treated subjects). CONCLUSION: Improvements in HRQOL were observed with abatacept, providing real-life tangible benefits to children with JIA and their parents/caregivers.
Keywords: Adolescent; Arthritis, Juvenile; Child; Double-Blind Method; Female; Health Status; Humans; Immunoconjugates; Male; Pain; Quality of Life; Questionnaires; Sleep Stages

Acute respiratory failure in a child after talc inhalation. - Patarino, Federica; Norbedo, Stefania; Barbi, Egidio; Poli, Furio; Furlan, Stefano; Savron, Fabio (Respiration, 2010)
Keywords: Female; Humans; Infant; Inhalation Exposure; Respiratory Insufficiency; Talc

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

Development of paediatric quality of inpatient care indicators for low-income countries - A Delphi study. - Ntoburi, Stephen; Hutchings, Andrew; Sanderson, Colin; Carpenter, James; Weber, Martin; English, Mike (BMC Pediatr, 2010)
BACKGROUND: Indicators of quality of care for children in hospitals in low-income countries have been proposed, but information on their perceived validity and acceptability is lacking. METHODS: Potential indicators representing structural and process aspects of care for six common conditions were selected from existing, largely qualitative WHO assessment tools and guidelines. We employed the Delphi technique, which combines expert opinion and existing scientific information, to assess their perceived validity and acceptability. Panels of experts, one representing an international panel and one a national (Kenyan) panel, were asked to rate the indicators over 3 rounds and 2 rounds respectively according to a variety of attributes. RESULTS: Based on a pre-specified consensus criteria most of the indicators presented to the experts were accepted: 112/137(82%) and 94/133(71%) for the international and local panels respectively. For the other indicators there was no consensus; none were rejected. Most indicators were rated highly on link to outcomes, reliability, relevance, actionability and priority but rated more poorly on feasibility of data collection under routine conditions. There was moderate to substantial agreement between the two panels of experts. CONCLUSIONS: This Delphi study provided evidence for the perceived usefulness of most of a set of measures of quality of hospital care for children proposed for use in low-income countries. However, both international and local experts expressed concerns that data for many process-based indicators may not currently be available. The feasibility of widespread quality assessment and responsiveness of indicators to intervention should be examined as part of continued efforts to improve approaches to informative hospital quality assessment.
Keywords: Child; Child, Hospitalized; Delphi Technique; Developing Countries; Expert Testimony; Female; Humans; Inpatients; Male; Pediatrics; Quality Indicators, Health Care; World Health Organization

Eltrombopag for the treatment of the inherited thrombocytopenia deriving from MYH9 mutations. - Pecci, Alessandro; Gresele, Paolo; Klersy, Catherine; Savoia, Anna; Noris, Patrizia; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Anna Maria; Melazzini, Federica; Balduini, Carlo L (Blood, 2010)
Platelet transfusion is currently the primary medical treatment for reducing thrombocytopenia in patients with inherited thrombocytopenias. To evaluate whether stimulating megakaryopoiesis could increase platelet count in these conditions, we treated patients with a severe thrombocytopenia induced by MYH9 mutations (MYH9-related disease) with a nonpeptide thrombopoietin receptor agonist, eltrombopag. Twelve adult patients with MYH9-RD and platelet counts of less than 50 × 10(9)/L received 50 mg of eltrombopag orally per day for 3 weeks. Patients who achieved a platelet count higher than 150 × 10(9)/L stopped therapy, those with 100 to 150 platelets × 10(9)/L continued treatment at the same eltrombopag dose for 3 additional weeks, while those with less than 100 platelets × 10(9)/L increased the eltrombopag dose to 75 mg for 3 weeks. Major responses (platelet count of at least 100 × 10(9)/L or 3 times the baseline value) were obtained in 8 patients, minor responses (platelet counts at least twice the baseline value) in 3. One patient did not respond. Bleeding tendency disappeared in 8 of 10 patients with bleeding symptoms at baseline. Mild adverse events were reported in 2 patients. The availability of thrombopoietin mimetics opened new prospects in the treatment of inherited thrombocytopenias. This study is registered at www.clinicaltrials.gov as NCT01133860 (European Union Drug Regulating Authorities Clinical Trials number 2008-001903-42).
Keywords: Administration, Oral; Adolescent; Adult; Benzoates; Dose-Response Relationship, Drug; Female; Genetic Predisposition to Disease; Humans; Hydrazines; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Platelet Aggregation; Platelet Count; Pyrazoles; Receptors, Thrombopoietin; Survival Rate; Thrombocytopenia; Treatment Outcome; Young Adult

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Fasting increases tobramycin oral absorption in mice. - De Leo, Luigina; Di Toro, Nicola; Decorti, Giuliana; Malusà, Noelia; Ventura, Alessandro; Not, Tarcisio (Antimicrob Agents Chemother, 2010)
The pharmacokinetics of the aminoglycoside tobramycin was evaluated after oral administration to fed or fasting (15 h) mice. As expected, under normal feeding conditions, oral absorption was negligible; however, fasting induced a dramatic increase in tobramycin bioavailability. The dual-sugar test with lactulose and l-rhamnose confirmed increased small bowel permeability via the paracellular route in fasting animals. When experiments aimed at increasing the oral bioavailability of hydrophilic compounds are performed, timing of fasting should be extremely accurate.
Keywords: Administration, Oral; Animals; Anti-Bacterial Agents; Biological Availability; Fasting; Injections, Intramuscular; Injections, Intravenous; Intestinal Absorption; Lactulose; Male; Mice; Mice, Inbred BALB C; Rhamnose; Tobramycin

Methotrexate withdrawal at 6 vs 12 months in juvenile idiopathic arthritis in remission: a randomized clinical trial. - Foell, Dirk; Wulffraat, Nico; Wedderburn, Lucy R; Wittkowski, Helmut; Frosch, Michael; Gerss, Joachim; Stanevicha, Valda; Mihaylova, Dimitrina; Ferriani, Virginia; Tsakalidou, Florence Kanakoudi; Foeldvari, Ivan; Cuttica, Ruben; et al. (JAMA, 2010)
CONTEXT: Novel therapies have improved the remission rate in chronic inflammatory disorders including juvenile idiopathic arthritis (JIA). Therefore, strategies of tapering therapy and reliable parameters for detecting subclinical inflammation have now become challenging questions. OBJECTIVES: To analyze whether longer methotrexate treatment during remission of JIA prevents flares after withdrawal of medication and whether specific biomarkers identify patients at risk for flares. DESIGN, SETTING, AND PATIENTS: Prospective, open, multicenter, medication-withdrawal randomized clinical trial including 364 patients (median age, 11.0 years) with JIA recruited in 61 centers from 29 countries between February 2005 and June 2006. Patients were included at first confirmation of clinical remission while continuing medication. At the time of therapy withdrawal, levels of the phagocyte activation marker myeloid-related proteins 8 and 14 heterocomplex (MRP8/14) were determined. INTERVENTION: Patients were randomly assigned to continue with methotrexate therapy for either 6 months (group 1 [n = 183]) or 12 months (group 2 [n = 181]) after induction of disease remission. MAIN OUTCOME MEASURES: Primary outcome was relapse rate in the 2 treatment groups; secondary outcome was time to relapse. In a prespecified cohort analysis, the prognostic accuracy of MRP8/14 concentrations for the risk of flares was assessed. RESULTS: Intention-to-treat analysis of the primary outcome revealed relapse within 24 months after the inclusion into the study in 98 of 183 patients (relapse rate, 56.7%) in group 1 and 94 of 181 (55.6%) in group 2. The odds ratio for group 1 vs group 2 was 1.02 (95% CI, 0.82-1.27; P = .86). The median relapse-free interval after inclusion was 21.0 months in group 1 and 23.0 months in group 2. The hazard ratio for group 1 vs group 2 was 1.07 (95% CI, 0.82-1.41; P = .61). Median follow-up duration after inclusion was 34.2 and 34.3 months in groups 1 and 2, respectively. Levels of MRP8/14 during remission were significantly higher in patients who subsequently developed flares (median, 715 [IQR, 320-1 110] ng/mL) compared with patients maintaining stable remission (400 [IQR, 220-800] ng/mL; P = .003). Low MRP8/14 levels indicated a low risk of flares within the next 3 months following the biomarker test (area under the receiver operating characteristic curve, 0.76; 95% CI, 0.62-0.90). CONCLUSIONS: In patients with JIA in remission, a 12-month vs 6-month withdrawal of methotrexate did not reduce the relapse rate. Higher MRP8/14 concentrations were associated with risk of relapse after discontinuing methotrexate. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN18186313.
Keywords: Adolescent; Antirheumatic Agents; Arthritis, Juvenile; ATP-Binding Cassette Transporters; Calgranulin B; Child; Child, Preschool; Female; Humans; Infant; Male; Methotrexate; Predictive Value of Tests; Prospective Studies; Recurrence; Remission Induction

Severe X-linked mitochondrial encephalomyopathy associated with a mutation in apoptosis-inducing factor. - Ghezzi, Daniele; Sevrioukova, Irina; Invernizzi, Federica; Lamperti, Costanza; Mora, Marina; d'Adamo, Pio; Novara, Francesca; Zuffardi, Orsetta; Uziel, Graziella; Zeviani, Massimo (Am J Hum Genet, 2010)
We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitochondrion-associated 1 precursor that deletes arginine 201 (R201 del). Under normal conditions, mature AIF is a FAD-dependent NADH oxidase of unknown function and is targeted to the mitochondrial intermembrane space (this form is called AIF(mit)). Upon apoptogenic stimuli, a soluble form (AIF(sol)) is released by proteolytic cleavage and migrates to the nucleus, where it induces "parthanatos," i.e., caspase-independent fragmentation of chromosomal DNA. In vitro, the AIF(R201 del) mutation decreases stability of both AIF(mit) and AIF(sol) and increases the AIF(sol) DNA binding affinity, a prerequisite for nuclear apoptosis. In AIF(R201 del) fibroblasts, staurosporine-induced parthanatos was markedly increased, whereas re-expression of AIF(wt) induced recovery of RC activities. Numerous TUNEL-positive, caspase 3-negative nuclei were visualized in patient #1's muscle, again indicating markedly increased parthanatos in the AIF(R201 del) critical tissues. We conclude that AIF(R201 del) is an unstable mutant variant associated with increased parthanatos-linked cell death. Our data suggest a role for AIF in RC integrity and mtDNA maintenance, at least in some tissues. Interestingly, riboflavin supplementation was associated with prolonged improvement of patient #1's neurological conditions, as well as correction of RC defects in mutant fibroblasts, suggesting that stabilization of the FAD binding in AIF(mit) is beneficial.
Keywords: Apoptosis; Apoptosis Inducing Factor; Caspase 3; Computer Simulation; Dietary Supplements; DNA Primers; DNA, Mitochondrial; Electron Transport; Female; Fibroblasts; Flavin-Adenine Dinucleotide; Genes, X-Linked; Humans; In Situ Nick-End Labeling; Infant, Newborn; Magnetic Resonance Imaging; Male; Mitochondrial Encephalomyopathies; Muscle, Skeletal; Mutation; Nervous System Diseases; Pedigree; Poly(ADP-ribose) Polymerases; Protein Conformation; Riboflavin; Staurosporine; Twins, Monozygotic

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Breastfeed Rev, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low-income settings, the original KMC modelis implemented. This consists of continuous (24 h/day; 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding and, adequate follow up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC modelin all types of settings was discussed at the 7th International Workshop on KMC Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents'role, modification of the NICU environment, performance of care in KMC, and KMCin case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Acta Paediatr, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low income settings, the original KMC model is implemented. This consists of continuous (24 h/day, 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding; and, adequate follow-up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC model in all types of settings was discussed at the 7th International Workshop on KMC. Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents' role, modification of the NICU environment, performance of care in KMC, and KMC in case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.
Keywords: Attitude of Health Personnel; Female; Humans; Infant Care; Infant, Newborn; Intensive Care Units, Neonatal; Male; Parent-Child Relations; Practice Guidelines as Topic; Professional-Patient Relations; Role; Skin; Visitors to Patients

[Strategies for cardiovascular prevention in children]. - Spinelli, Angela; Nardone, Paola; Lamberti, Anna; Baglio, Giovanni (G Ital Cardiol (Rome), 2010)
Keywords: Body Mass Index; Cardiovascular Diseases; Child; Diet, Mediterranean; Food Habits; Humans; Life Style; Motor Activity; Obesity; Overweight; Patient Education as Topic; Population Surveillance; Questionnaires; Risk Factors

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Ticks and Lyme borreliosis in an alpine area in northeast Italy. - Nazzi, F; Martinelli, E; Del Fabbro, S; Bernardinelli, I; Milani, N; Iob, A; Pischiutti, P; Campello, C; D'Agaro, P (Med Vet Entomol, 2010)
A 2-year study was conducted in a mountainous area of northeast Italy to evaluate the occurrence and distribution of ticks, as well as to assess the prevalence of the spirochaete Borrelia burgdorferi sensu lato. All ticks collected were Ixodes ricinus L. (Parasitiformes: Ixodidae). In general, most nymphs and adult ticks were collected from April to July. Tick density was highly variable among sites; however, two areas with different infestation levels were recognized. Prevalences of B. burgdorferi s.l. in nymphal stages were rather variable between sites; overall the prevalence of infected nymphs in the whole area was slightly higher than 20%. The prevalence of B. burgdorferi s.l. in nymphs does not seem to be correlated with nymph density. The correlation between the incidence of Lyme borreliosis (reported human cases/1000 inhabitants/year) and Borrelia prevalence in nymphs was not significant, although a significant correlation was found between borreliosis incidence and nymph density.
Keywords: Animals; Borrelia burgdorferi; Climate; Ecology; Humans; Incidence; Italy; Ixodes; Lyme Disease; Nymph; Population Density; Prevalence; Seasons; Ticks

Toward a consensus on guiding principles for health systems strengthening. - Swanson, Robert C; Bongiovanni, Annette; Bradley, Elizabeth; Murugan, Varnee; Sundewall, Jesper; Betigeri, Arvind; Nyonator, Frank; Cattaneo, Adriano; Harless, Brandi; Ostrovsky, Andrey; Labonté, Ronald (PLoS Med, 2010)
Keywords: Global Health; Humans; Public Health

Towards universal Kangaroo Mother Care: recommendations and report from the First European conference and Seventh International Workshop on Kangaroo Mother Care. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ibe, O; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Ruiz Peláez, J G; et al. (Acta Paediatr, 2010)
UNLABELLED: The hallmark of Kangaroo Mother Care (KMC) is the kangaroo position: the infant is cared for skin-to-skin vertically between the mother's breasts and below her clothes, 24 h/day, with father/substitute(s) participating as KMC providers. Intermittent KMC (for short periods once or a few times per day, for a variable number of days) is commonly employed in high-tech neonatal intensive care units. These two modalities should be regarded as a progressive adaptation of the mother-infant dyad, ideally towards continuous KMC, starting gradually and progressively with intermittent KMC. The other components in KMC are exclusive breastfeeding (ideally) and early discharge in kangaroo position with strict follow-up. Current evidence allows the following general statements about KMC in affluent and low-income settings: KMC enhances bonding and attachment; reduces maternal postpartum depression symptoms; enhances infant physiologic stability and reduces pain, increases parental sensitivity to infant cues; contributes to the establishment and longer duration of breastfeeding and has positive effects on infant development and infant/parent interaction. Therefore, intrapartum and postnatal care in all types of settings should adhere to a paradigm of nonseparation of infants and their mothers/families. Preterm/low-birth-weight infants should be regarded as extero-gestational foetuses needing skin-to-skin contact to promote maturation. CONCLUSION: Kangaroo Mother Care should begin as soon as possible after birth, be applied as continuous skin-to-skin contact to the extent that this is possible and appropriate and continue for as long as appropriate.
Keywords: Congresses as Topic; Female; Global Health; Humans; Infant Care; Infant, Newborn; Male; Parent-Child Relations; Practice Guidelines as Topic; Randomized Controlled Trials as Topic; Skin

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal